Optical stack

JP2026167557APending Publication Date: 2026-10-14SUMITOMO CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2026048897
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-03-31
Filing Date
2026-03-24
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0006】 本発明によれば、良好な耐久性を示す光学積層体を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026167557000001
    Figure 2026167557000001
  • Figure 2026167557000002
    Figure 2026167557000002
  • Figure 2026167557000003
    Figure 2026167557000003
Patent Text Reader

Abstract

To provide an optical laminate that exhibits good durability. [Solution] An optical laminate comprising a polarizing film, a resin layer X, and a resin layer Y adjacent to each other in this order, The polarizing film comprises a cured layer of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound and a dichroic dye. The contact angle of water with respect to the surface of the resin layer X is 90° or less. The resin layer Y is a cured layer of a resin composition (Y) containing a curable compound, wherein the curable composition comprises a polyfunctional (meth)acrylate compound (Y1) having a molecular weight of less than 1000 g / mol, and a (meth)acrylate compound (Y2) having one (meth)acrylic group and one hydroxyl group in its molecule, in an optical laminate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to an optical laminate. [Background technology]

[0002] Polarizers are components that make up various image display panels, such as liquid crystal display panels and organic EL display panels. In recent years, with the demand for thinner image display panels, polarizing films formed by coating with a composition containing a liquid crystal compound and a dichroic dye have been widely used (Patent Documents 1 and 2). [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2020-46622 [Patent Document 2] Japanese Patent Publication No. 2019-203949 [Overview of the Initiative] [Problems that the invention aims to solve]

[0004] Polarizers composed of liquid crystal compounds and dichroic dyes may experience a decrease in polarization performance over time due to the disruption of anisotropy, as the dichroic dye contained within the polarizer can easily diffuse outward depending on the environmental conditions to which it is exposed. In recent years, image display devices have been used in a variety of environments, and consequently, there is a need for further improvements in the durability of optical laminates that possess polarization performance. The present invention aims to provide an optical laminate that exhibits good durability. [Means for solving the problem]

[0005] The present inventors, after diligent study to solve the above problems, have completed the present invention. That is, the present invention encompasses the following preferred embodiments. [1] An optical laminate comprising a polarizing film, a resin layer X, and a resin layer Y adjacent to each other in this order, The polarizing film comprises a cured layer of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound and a dichroic dye. The contact angle of water with respect to the surface of the resin layer X is 90° or less. The resin layer Y is a cured layer of a resin composition (Y) containing a curable compound, wherein the curable composition comprises a polyfunctional (meth)acrylate compound (Y1) having a molecular weight of less than 1000 g / mol, and a (meth)acrylate compound (Y2) having one (meth)acrylic group and one hydroxyl group in its molecule, in an optical laminate. [2] The optical laminate according to [1], wherein the resin composition (Y) further comprises a polyfunctional urethane (meth)acrylate compound (Y3) having a weight-average molecular weight of 1000 g / mol or more. [3] The optical laminate according to [1] or [2], wherein the resin composition (Y) further comprises a (meth)acrylate compound (Y4) having an aromatic ring but no hydroxyl group in the molecule. [4] The optical laminate according to [2], wherein the total content of the polyfunctional (meth)acrylate compound (Y1) and the polyfunctional urethane (meth)acrylate compound (Y3) is 10 to 70 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y). [5] The optical laminate according to any one of [1] to [4], wherein the content of the (meth)acrylate compound (Y2) is 25 to 80 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y). [6] The optical laminate according to [3], wherein the content of the (meth)acrylate compound (Y4) is 5 to 25 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y). [7] The optical laminate according to any one of [1] to [6], wherein the resin layer X is a cured layer of a polyvinyl alcohol-based resin composition. [8] The optical laminate according to any one of [1] to [7], wherein the resin layer Y contains a phase difference film adjacent to the resin layer X, and the phase difference film contains a cured layer of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound. [9] The optical laminate according to [8], wherein the phase difference film includes an alignment film, and the alignment film is located on the resin layer Y side.

[10] The optical laminate according to any one of [1] to [9], wherein the resin composition (Y) contains 1 to 10 parts by mass of a polymerization initiator per 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y).

[11] The polymerization initiator has a molar extinction coefficient of 10 L·mol at a light source wavelength of 400 nm under acetonitrile solvent. -1 ·cm -1 The optical laminate described above

[10] .

[12] When the in-plane average refractive index of the resin layer X is n1, the in-plane average refractive index of the resin layer Y is n2, and the in-plane average refractive index of the phase difference film is n3, then the following equation (1): |(n1×n3) 1 / 2 -n²| ≤ 0.05 (1) The optical laminate according to [8] or [9], which satisfies the condition. [Effects of the Invention]

[0006] According to the present invention, it is possible to provide an optical laminate that exhibits good durability. [Modes for carrying out the invention]

[0007] The embodiments of the present invention will be described in detail below. However, the scope of the present invention is not limited to the embodiments described herein, and various modifications can be made without impairing the spirit of the invention.

[0008] <Resin layer X> The optical laminate of the present invention comprises a polarizing film, a resin layer X, and a resin layer Y adjacent to each other in this order. In the optical laminate of the present invention, the polarizing film comprises a cured layer of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound and a dichroic dye (hereinafter also referred to as the "liquid crystal polarizing film"), and a resin layer X having a water contact angle of 90° or less on its surface is laminated adjacent to the polarizing film. The resin layer X adjacent to the polarizing film containing the liquid crystal polarizing film functions as a layer that suppresses the diffusion of the dichroic dye from the liquid crystal polarizing film to other layers. The water contact angle with the surface of the resin layer X (hereinafter also referred to as the "water contact angle") is 90° or less, and the resin layer X usually has relatively high polarity. The polarity of dichroic dyes used in polarizing films is generally relatively low. Therefore, the large difference in polarity between the resin layer X, which has a water contact angle of 90° or less, and the dichroic dye makes it possible to suppress the diffusion of the dichroic dye from the polarizing film. From the viewpoint of further enhancing the diffusion-suppressing effect of such dichroic dyes, in one embodiment of the present invention, the water contact angle of the resin layer X is preferably 85° or less, more preferably 80° or less. Furthermore, the lower limit of the water contact angle of the resin layer X is usually 55° or more, preferably 60° or more. When the water contact angle of the resin layer X is above the aforementioned lower limit, it is preferable not only for the high diffusion-suppressing effect of the dichroic dyes but also for the effect of improving the humidity and heat resistance of the optical laminate. The water contact angle of the resin layer X can be measured, for example, using a contact angle measuring device in accordance with the method described in JIS R3257:1999. Note that if the water contact angles differ on both sides of the resin layer X, the above water contact angle refers to the water contact angle on the side in contact with the polarizing film.

[0009] The water contact angle of the resin layer X can be controlled, for example, by the type of resin constituting the resin layer X, its combination, chemical modification, surface treatment of the resin layer X (e.g., plasma treatment, corona discharge treatment), heat treatment, etc.

[0010] In the present invention, the layer is not particularly limited as long as the water contact angle with respect to the layer surface is 90° or less, and may be a layer formed from a resin composition containing known resin materials (hereinafter also referred to as "resin composition (X)"). For example, if the resin composition contains a water-soluble polymer, the water contact angle of the resulting resin layer can be reduced, and it is easy to obtain a layer with a water contact angle of 90° or less. Therefore, in one embodiment of the present invention, the resin layer X is preferably a layer formed from a resin composition containing a water-soluble polymer.

[0011] Examples of water-soluble polymers constituting the resin composition (X) include polyacrylamide polymers; vinyl alcohol polymers such as polyvinyl alcohol and ethylene-vinyl alcohol copolymers, (meth)acrylic acid or its anhydride-vinyl alcohol copolymers; carboxyvinyl polymers; polyvinylpyrrolidone; starches; sodium alginate; or polyethylene oxide polymers. These polymers may be used individually or in combination of two or more. In particular, the water-soluble polymer forming the resin layer X is preferably a polyvinyl alcohol polymer because it has high hydrophilicity and excellent shielding effect on dichroic dyes in the polarizing film. In one embodiment of the present invention, the resin layer X is preferably a cured layer of a composition containing a polyvinyl alcohol resin (polyvinyl alcohol resin composition).

[0012] The polyvinyl alcohol-based resin may be a modified polyvinyl alcohol-based resin, such as a partially saponified polyvinyl alcohol or a fully saponified polyvinyl alcohol, as well as a carboxyl-modified polyvinyl alcohol, an acetoacetyl-modified polyvinyl alcohol, anion-modified polyvinyl alcohol resin, a methylol-modified polyvinyl alcohol, or an amino-modified polyvinyl alcohol. Alternatively, a commercially available polyvinyl alcohol-based resin may be used. In one embodiment of the present invention, it is preferable that the water-soluble polymer constituting the resin composition (X) contains acetoacetyl-modified polyvinyl alcohol.

[0013] If the resin layer X is a layer formed from a water-soluble polymer, the content of the water-soluble polymer in the layer is preferably 75% by mass or more, more preferably 80% by mass or more, and even more preferably 85% by mass or more, with an upper limit of 100% by mass.

[0014] The resin composition (X) is usually prepared as a solution in which a resin material such as a water-soluble polymer is dissolved in a solvent. The solvent can be selected according to the resin material used, but typically examples include water, alcohol, or a mixture of water and alcohol, with water being preferred.

[0015] The solid content concentration of the resin composition (X) obtained by adding a solvent to the components constituting the resin layer X, such as a water-soluble polymer, is preferably 1 to 50% by mass, more preferably 2 to 30% by mass. When the solid content concentration of the resin composition (X) is within the above range, the viscosity of the composition tends to be low, resulting in good coating properties and handling properties. In this specification, the solid content of the resin composition (X) means all components of the resin composition (X) excluding volatile components such as organic solvents. Hereafter, when the term "solid content" is used in this specification, it similarly refers to the components of the target composition excluding volatile components such as solvents.

[0016] The resin composition (X) may contain other components such as additives, obtained by adding a solvent such as water to a resin material such as a water-soluble polymer. Examples of such other components include crosslinking agents, preservatives, and leveling agents. If the resin composition (X) contains other components such as additives, the amount thereof is preferably 10% by mass or less, more preferably 5% by mass or less, based on the solid content of the resin composition.

[0017] The resin layer X can be obtained, for example, by coating a resin composition (X) onto a polarizing film and drying and curing the coating film.

[0018] The method for applying the resin composition (X) is not particularly limited and includes known methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and applicator coating, as well as printing methods such as flexographic coating.

[0019] The drying temperature and time for forming the resin layer X from the coating film of the resin composition (X) are not particularly limited and can be appropriately determined according to the composition of the resin composition (X) used. The drying process can be carried out, for example, by blowing hot air, and the temperature is usually in the range of 40 to 100°C, preferably 60 to 100°C. The drying time is usually 10 seconds to 10 minutes.

[0020] The thickness of the resin layer X is not particularly limited and can be appropriately determined depending on the application of the optical laminate. In one embodiment of the present invention, from the viewpoint of thinning the optical laminate, the thickness of the resin layer X is preferably 0.01 μm or more and 5 μm or less, preferably 4 μm or less, more preferably 3 μm or less, and even more preferably 2 μm or less. The thickness of the resin layer X can be measured using a laser microscope, a film thickness gauge, etc. The same method is used to measure the thickness of each layer constituting the optical laminate, such as the resin layer Y and the polarizing film.

[0021] The resin layer X may be a layer having a water contact angle of 90° or less due to surface treatment. Examples of surface treatments include corona discharge treatment and plasma treatment. In this case, the resin constituting the resin layer may be the water-soluble polymer mentioned above.

[0022] <Resin layer Y> The optical laminate of the present invention includes a resin layer Y adjacent to the resin layer X on the opposite side of the polarizing film. The resin layer Y is a cured layer of a resin composition containing a curable compound (hereinafter also referred to as "resin composition (Y)"). The cured layer of a resin composition containing a curable compound is a layer obtained by curing (polymerizing) the curable compound contained in a coating film after obtaining a coating film of the resin composition. That is, the cured layer of the resin composition is a layer that contains a cured product (polymer) of the curable compound. The resin composition (Y) includes, as a curable compound, a polyfunctional (meth)acrylate compound with a molecular weight of less than 1000 g / mol (hereinafter also referred to as "polyfunctional (meth)acrylate compound (Y1)") and a monofunctional (meth)acrylate compound having one (meth)acrylic group and one hydroxyl group in its molecule (hereinafter also referred to as "hydroxyl group-containing (meth)acrylate compound (Y2)"). Note that the polyfunctional (meth)acrylate compound is a compound having two or more (meth)acrylic groups in its molecule.

[0023] While the aforementioned resin layer X can exhibit a high inhibitory effect against the diffusion of dichroic dyes even in high-temperature environments, if it is highly polar and hydrophilic, the diffusion prevention effect of dichroic dyes may decrease under high humidity conditions. In the present invention, the resin layer Y, which is composed of a polymer of a polyfunctional (meth)acrylate compound (Y1) and a hydroxyl group-containing (meth)acrylate compound (Y2), can function as a layer that prevents the migration of dichroic dyes from the resin layer X to the outside (towards the resin layer Y) under high humidity conditions. This makes it possible to improve the heat and humidity resistance of the optical laminate, and to obtain an optical laminate that has an excellent diffusion prevention effect against dichroic dyes and can maintain high polarization performance even in harsh environments of high temperature and high humidity. Furthermore, for example, in a laminate in which a phase difference film as described later is laminated as a component, the migration of dichroic dyes from the polarizing film to the phase difference film under high temperature and high humidity conditions can be suppressed more effectively, and an optical laminate such as a circular polarizer can be obtained that has high durability and excellent optical properties. Furthermore, the resin layer Y, which is composed of a polymer of a polyfunctional (meth)acrylate compound (Y1) and a hydroxyl group-containing (meth)acrylate compound (Y2), has a function to prevent the diffusion of dichroic dyes and can ensure high adhesion between the resin layer Y and the layer laminated on the opposite side of the resin layer X. For this reason, it is advantageous in that, for example, a phase difference film can be placed adjacent to the resin layer Y with high adhesion. In this specification, "durability" of an optical laminate refers to the property of being able to suppress the deterioration of polarization performance even in high temperature and / or high humidity environments, and increased or improved durability means that the deterioration or change in polarization performance in high temperature and / or high humidity environments becomes smaller. Also, when simply expressed as "adhesion of resin layer Y," the adhesion refers to the adhesion between the resin layer Y and the layer located on the opposite side of the resin layer Y from the resin layer X.

[0024] The polyfunctional (meth)acrylate compound (Y1) functions as a component that introduces a cross-linked structure into the resin layer Y, and is a component that can contribute to improving the heat and humidity resistance of the optical laminate. By including the polyfunctional (meth)acrylate compound (Y1) in the resin composition (Y), the resin layer Y obtained from the composition can suppress the migration of dichroic dyes in the polarizing film beyond the resin layer X to other layers (typically, such as the phase difference film described later) in a heat and humidity environment. One type of polyfunctional (meth)acrylate compound (Y1) may be used, or two or more types may be used in combination.

[0025] For example, a polyfunctional (meth)acrylate compound (Y1) is: Alkylene glycol di(meth)acrylates such as ethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate and neopentyl glycol di(meth)acrylate; halogen-substituted alkylene glycol di(meth)acrylates such as diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetrafluoroethylene glycol di(meth)acrylate; trimethylolpropane di(meth)acrylate, ditrimethyl Di(meth)acrylates of aliphatic polyols such as tyrolpropane di(meth)acrylate and pentaerythritol di(meth)acrylate; di(meth)acrylates of hydrogenated dicyclopentadiene or tricyclodecane dialkanol such as hydrogenated dicyclopentadienyl di(meth)acrylate and tricyclodecane dimethanol di(meth)acrylate; di(meth)acrylates of dioxane glycol or dioxane dialkanol such as 1,3-dioxane-2,5-diyl di(meth)acrylate (also known as dioxane glycol di(meth)acrylate); di(meth)acrylates of neopentyl glycol ester hydroxypivalate; difunctional (meth)acrylates such as tris(hydroxyethyl) isocyanurate di(meth)acrylate; Trifunctional (meth)acrylates such as glycerin tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate; caprolactone-modified trimethylolpropane tri(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, ethylene oxide-modified trimethylolpropane tri(meth)acrylate, ethylene oxide-modified pentaerythritol tri(meth)acrylate, propylene oxide-modified trimethylolpropane tri(meth)acrylate, propylene oxide-modified pentaerythritol tri(meth)acrylate, isocyanurate tri(meth)acrylate, etc. Tetrafunctional (meth)acrylates such as ditrimethylolpropanetetra(meth)acrylate, pentaerythritoltetra(meth)acrylate, dipentaerythritoltetra(meth)acrylate, tripentaerythritoltetra(meth)acrylate, caprolactone-modified pentaerythritoltetra(meth)acrylate, caprolactone-modified tripentaerythritoltetra(meth)acrylate, ethylene oxide-modified pentaerythritoltetra(meth)acrylate, ethylene oxide-modified tripentaerythritoltetra(meth)acrylate, propylene oxide-modified pentaerythritoltetra(meth)acrylate, and propylene oxide-modified tripentaerythritoltetra(meth)acrylate; Pentafunctional (meth)acrylates such as dipentaerythritol penta(meth)acrylate, tripentaerythritol penta(meth)acrylate; caprolactone-modified dipentaerythritol penta(meth)acrylate, caprolactone-modified tripentaerythritol penta(meth)acrylate, ethylene oxide-modified dipentaerythritol penta(meth)acrylate, ethylene oxide-modified tripentaerythritol penta(meth)acrylate, propylene oxide-modified dipentaerythritol penta(meth)acrylate, propylene oxide-modified tripentaerythritol penta(meth)acrylate; and Hexafunctional (meth)acrylates such as dipentaerythritol hexa(meth)acrylate, tripentaerythritol hexa(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, caprolactone-modified tripentaerythritol hexa(meth)acrylate, ethylene oxide-modified dipentaerythritol hexa(meth)acrylate, ethylene oxide-modified tripentaerythritol hexa(meth)acrylate, propylene oxide-modified dipentaerythritol hexa(meth)acrylate, and propylene oxide-modified tripentaerythritol hexa(meth)acrylate. These are some examples.

[0026] By controlling the molecular weight between crosslinking points and the number of crosslinking points of the polyfunctional (meth)acrylate compound (Y1), the crosslinking structure in the resin layer Y can be controlled, thereby improving its resistance to humid heat. Generally, the smaller the molecular weight between crosslinking points and the greater the number of crosslinking points, the denser the crosslinking structure tends to be. In the present invention, the molecular weight of the polyfunctional (meth)acrylate compound (Y1) is less than 1000 g / mol, preferably 900 g / mol or less, more preferably 800 g / mol or less, and preferably 300 g / mol or more, more preferably 400 g / mol or more. In one embodiment of the present invention, the number of (meth)acrylic groups in the polyfunctional (meth)acrylate compound (Y1) is preferably 4 or more, more preferably 5 or more, preferably 10 or less, more preferably 8 or less, and particularly preferably 6. If the molecular weight and / or the number of (meth)acrylic groups of the polyfunctional (meth)acrylate compound (Y1) are within the above range, the crosslinking density of the resin layer Y can be appropriately increased, thereby enhancing the diffusion prevention effect on dichroic dyes even in high-temperature and high-humidity environments. Furthermore, if the crosslinking density of the resin layer Y becomes too high, the adhesion between the resin layer Y and the layer laminated on the opposite side of the resin layer X may decrease. However, by controlling the inter-crosslinking molecular weight and the number of crosslinking points of the polyfunctional (meth)acrylate compound (Y1) within the above range, the crosslinking density of the resin layer Y can be appropriately increased, which is advantageous in that layers adjacent to the resin layer Y, such as a phase difference film, can be positioned adjacent to the resin layer Y with high adhesion. In particular, if the molecular weight and the number of (meth)acrylic groups of the polyfunctional (meth)acrylate compound (Y1) are both within the above range, the durability of the optical laminate in high-temperature and high-humidity environments, and the adhesion between the resin layer Y and adjacent layers can be further improved.

[0027] The content of the polyfunctional (meth)acrylate compound (Y1) in the resin composition (Y) (the total amount if two or more types are included) is preferably 5 to 55 parts by mass, more preferably 5 to 50 parts by mass, and even more preferably 5 to 40 parts by mass, per 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y), and may be, for example, 10 to 35 parts by mass or 15 to 35 parts by mass. When the content of the polyfunctional (meth)acrylate compound (Y1) is within the above range, the crosslinking structure of the resulting resin layer Y can be easily controlled, and the diffusion prevention effect on dichroic dyes can be enhanced even in high temperature and high humidity environments. This improves the durability of the optical laminate in high temperature and high humidity environments.

[0028] The hydroxyl group-containing (meth)acrylate compound (Y2) can improve the heat resistance of the resin layer Y and can also function as an adhesion imparting agent. From the viewpoint of improving heat resistance and adhesion, the number of hydroxyl groups in the hydroxyl group-containing (meth)acrylate compound (Y2) is preferably 1 to 5, more preferably 1 to 2, and even more preferably 1. The hydroxyl group-containing (meth)acrylate compound (Y2) is not particularly limited and can be selected from known (meth)acrylate compounds having hydroxyl groups. Specifically, examples include hydroxyalkyl (meth)acrylates having 4 to 16 carbon atoms, hydroxycycloalkyl (meth)acrylates having 4 to 16 carbon atoms, hydroxyalkylated phenyl (meth)acrylates having 2 to 14 carbon atoms, polyethylene glycol (meth)acrylates, hydroxy(di)alkyl (meth)acrylamides having 4 to 16 carbon atoms, hydroxyalkylated phenyl (meth)acrylamides having 2 to 14 carbon atoms, polyethylene glycol (meth)acrylamides, and the like. Preferred examples are hydroxyalkyl (meth)acrylates having 4 to 8 carbon atoms and hydroxycycloalkyl (meth)acrylates having 4 to 16 carbon atoms, and more preferred examples are hydroxyalkyl acrylates having 4 to 8 carbon atoms and hydroxycycloalkyl acrylates having 4 to 16 carbon atoms. The hydroxyl group-containing (meth)acrylate compound (Y2) may be used alone or in combination of two or more types.

[0029] The content of hydroxyl group-containing (meth)acrylate compound (Y2) in the resin composition (Y) (the total amount if two or more types are included) is preferably 25 to 80 parts by mass, more preferably 30 to 75 parts by mass, and even more preferably 35 to 65 parts by mass, based on 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y). When the content of hydroxyl group-containing (meth)acrylate compound (Y2) is within the above range, the heat resistance of the resulting resin layer Y can be further enhanced. Furthermore, the adhesion between the resin layer Y and the layer adjacent to the resin layer Y can be improved, so for example, a phase difference film, as described later, can be directly laminated onto the resin layer Y without the need for an adhesive layer or other adhesive layer. In addition, the hydroxyl group-containing (meth)acrylate compound (Y2) also contributes to adjusting the viscosity of the resin composition (Y), and can impart good coating properties to the resin composition (Y).

[0030] In one embodiment of the present invention, the mass ratio (polyfunctional (meth)acrylate compound (Y1) / hydroxyl group-containing (meth)acrylate compound (Y2)) contained in the resin composition (Y) is preferably 0.05 to 3.0, more preferably 0.2 to 1.5, and even more preferably 0.3 to 1.0. When the mass ratio of the polyfunctional (meth)acrylate compound to the hydroxyl group-containing (meth)acrylate compound is within the above range, an optical laminate can be obtained that has a good balance of durability and interlayer adhesion in a high-temperature, high-humidity environment.

[0031] The resin composition (Y) preferably contains a polyfunctional urethane (meth)acrylate compound (Y3) (hereinafter also referred to as "urethane (meth)acrylate compound (Y3)") having a weight-average molecular weight of 1000 g / mol or more. Urethane (meth)acrylate is generally a reaction product of an isocyanate compound, a polyol compound, and a (meth)acrylate compound. The urethane (meth)acrylate compound (Y3) contains a urethane bond in its molecule and has two or more (meth)acrylic groups. One type of urethane (meth)acrylate compound (Y3) may be used, or two or more types may be used in combination. In addition, commercially available products may be used as the urethane (meth)acrylate compound (Y3).

[0032] The urethane (meth)acrylate compound (Y3) can impart appropriate toughness while forming a cross-linked structure, thereby contributing to improved adhesion to adjacent layers. It is also suitable as a component for adjusting the viscosity of the resin composition (Y), thereby improving the coatability of the resin composition (Y). From the viewpoint of durability in high temperature and high humidity environments, adhesion of the resin layer Y, and coatability of the resin composition (Y), the number of (meth)acrylic groups contained in the molecule of the urethane (meth)acrylate compound (Y3) is preferably 3 or more, more preferably 4 or more, preferably 8 or less, and more preferably 7 or less. Similarly, the weight-average molecular weight of the urethane (meth)acrylate compound (Y3) is preferably 1050 g / mol or more, preferably 20000 g / mol or less, and more preferably 3000 g / mol or less. The weight-average molecular weight can be measured, for example, by gel permeation chromatography (GPC).

[0033] When the resin composition (Y) contains a urethane (meth)acrylate compound (Y3), its content (or the total amount if it contains two or more types) is preferably 1 to 50 parts by mass, more preferably 5 to 45 parts by mass, and even more preferably 5 to 40 parts by mass, based on 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y). For example, it may be 10 to 40 parts by mass, 15 to 35 parts by mass, or 20 to 35 parts by mass. When the content of the urethane (meth)acrylate compound (Y3) is within the above range, the viscosity of the resin composition (Y) can be easily controlled, and the coating properties can be improved. Furthermore, the adhesion of the resulting resin layer Y can be further improved.

[0034] In one embodiment of the present invention, the resin composition (Y) preferably contains a polyfunctional (meth)acrylate compound (Y1) and a urethane (meth)acrylate compound (Y3) as polyfunctional (meth)acrylate compounds. By including at least two different polyfunctional (meth)acrylate compounds as polyfunctional (meth)acrylate compounds, the crosslinking density can be easily controlled within an appropriate range, improving the durability of the optical laminate in high-temperature and high-humidity environments, and also improving the adhesion of the resin layer Y. In one embodiment of the present invention, when the resin composition (Y) contains a polyfunctional (meth)acrylate compound (Y1) and a urethane (meth)acrylate compound (Y3), the total content of these is preferably 10 to 70 parts by mass, more preferably 10 to 60 parts by mass, based on 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y), and may be, for example, 20 to 60 parts by mass, 25 to 60 parts by mass, or 25 to 50 parts by mass.

[0035] In one embodiment of the present invention, the mass ratio of the polyfunctional (meth)acrylate compound (Y1) to the urethane (meth)acrylate compound (Y3) in the resin composition (Y) (polyfunctional (meth)acrylate compound (Y1) / urethane (meth)acrylate compound (Y3)) is preferably 0.3 to 2.0, more preferably 0.5 to 2.0, and even more preferably 0.6 to 1.8. When the mass ratio of the polyfunctional (meth)acrylate compound (Y1) to the urethane (meth)acrylate compound (Y3) is within the above range, an optical laminate can be obtained that combines moisture and heat resistance with interlayer adhesion.

[0036] In the present invention, the resin composition (Y) may contain a monofunctional (meth)acrylate compound having an aromatic ring but no hydroxyl group in its molecule (hereinafter also referred to as "aromatic ring-containing (meth)acrylate compound (Y4)"). The aromatic ring-containing (meth)acrylate compound (Y4) can function as a high refractive index agent in the resin layer Y. Therefore, for example, when a liquid crystal cured film such as a phase difference film is adjacent to the resin layer Y, it becomes easier to approximate the in-plane average refractive index of the resin layer Y with the in-plane average refractive index of the phase difference film adjacent to the resin layer Y. The aromatic ring-containing (meth)acrylate compound (Y4) is a compound having one or more aromatic rings in its molecule, but the number of aromatic rings contained in the molecule is preferably 1 to 5, more preferably 1 to 3, and even more preferably 2. Examples of aromatic rings include benzene rings, biphenyl rings, and polycyclic aromatic rings. When the aromatic ring (meth)acrylate compound (Y4) contains multiple aromatic rings, they may be the same or different from each other. As the aromatic ring-containing (meth)acrylate compound (Y4), one type may be used alone, or two or more types may be used in combination.

[0037] Examples of aromatic ring-containing (meth)acrylate compounds (Y4) include ethoxylated-o-phenylphenol acrylate, bisphenol A type epoxy (meth)acrylate, bisphenol F type epoxy (meth)acrylate, 2-([1,1'-biphenyl]-2-yloxy)ethyl acrylate, 3-phenoxybenzyl acrylate, naphthalene-1-yl methyl acrylate, 2-(2-([1,1'-biphenyl]-2-yloxy)ethoxy)ethyl acrylate, (naphthalene-1-ylmethoxy)methyl acrylate, 6-((4'-cyano-[1,1'-biphenyl]-4-yl)oxy)hexyl acrylate, 4-benzoylphenyl acrylate, anthracene-9-yl methyl acrylate, and [1,1'-biphenyl)-4,4'-diyl diacrylate, with ethoxylated-o-phenylphenol acrylate being preferred.

[0038] The refractive index of the aromatic ring-containing (meth)acrylate compound (Y4) is preferably 1.50 to 1.65, more preferably 1.55 to 1.60, and even more preferably 1.57 to 1.59. When the refractive index of the aromatic ring-containing (meth)acrylate compound (Y4) is within the above range, its function as a high refractive index agent is sufficiently obtained, and an effect of suppressing the increase in reflectivity in optical laminates can be expected.

[0039] When a monofunctional (meth)acrylate compound contains an aromatic ring-containing (meth)acrylate compound (Y4), its content (or the total amount if it contains two or more) is preferably 5 to 25 parts by mass, more preferably 5 to 20 parts by mass, and even more preferably 10 to 20 parts by mass, based on 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y). When the content of the aromatic ring-containing (meth)acrylate compound (Y4) is within the above range, it is possible to expect an effect of suppressing the increase in reflectivity at the interface with the phase difference layer when a phase difference film is provided adjacent to the resin layer X and the resin layer Y, while simultaneously ensuring high adhesion between the resin layer Y, such as the phase difference layer, and adjacent layers.

[0040] The resin composition (Y) forming the resin layer Y may contain curable compounds other than polyfunctional (meth)acrylate compounds (Y1), hydroxyl group-containing (meth)acrylate compounds (Y2), urethane (meth)acrylate compounds (Y3), and aromatic ring-containing (meth)acrylate compounds (Y4) (hereinafter also referred to as "other curable compounds"). Examples of such other curable compounds include polyfunctional (meth)acrylate compounds having a weight-average molecular weight of 1000 g / mol or more and not having urethane bonds, and monofunctional (meth)acrylate compounds that do not contain hydroxyl groups or aromatic rings in their molecules.

[0041] If the resin composition (Y) contains other curable compounds, the amount thereof is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, in total, per 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y), and may be, for example, 10 parts by mass or less or 5 parts by mass or less. When the amount of other curable compounds is within the above range, the effects of the present invention obtained by the polyfunctional (meth)acrylate compound (Y1), hydroxyl group-containing (meth)acrylate compound (Y2), and optionally included urethane (meth)acrylate compound (Y3) and aromatic ring-containing (meth)acrylate compound (Y4) can be fully ensured. In one embodiment of the present invention, the resin composition (Y) does not have to contain other curable compounds.

[0042] In one embodiment of the present invention, the mass ratio (polyfunctional (meth)acrylate compound / monofunctional (meth)acrylate compound) of the polyfunctional (meth)acrylate compound contained in the resin composition (Y) is preferably 0.1 to 3.0, more preferably 0.3 to 2.5, and even more preferably 0.5 to 2.0. When the mass ratio of the polyfunctional (meth)acrylate compound to the monofunctional (meth)acrylate compound is within the above range, an optical laminate can be obtained that has a good balance of durability and interlayer adhesion in high temperature and high humidity environments.

[0043] Furthermore, in one embodiment of the present invention, the number of functional groups of the polyfunctional curable compounds (particularly polyfunctional (meth)acrylate compounds) contained in the resin composition (Y) is preferably 2 to 10, more preferably 4 to 8. In other words, it is preferable that the resin composition (Y) substantially does not contain polyfunctional curable compounds with 12 or more functional groups. The amount of polyfunctional curable compounds with 12 or more functional groups (preferably 10 or more or 8 or more) is preferably 1 part by mass or less, more preferably 0.5 parts by mass or less, per 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y). When the content of polyfunctional curable compounds with a large number of functional groups is within the above range, an optical laminate can be obtained that has a good balance of durability in high temperature and high humidity environments and interlayer adhesion.

[0044] The resin composition (Y) may contain a polymerization initiator. The polymerization initiator is a compound that can initiate the polymerization reaction of curable compounds such as a polyfunctional (meth)acrylate compound (Y1), a hydroxyl group-containing (meth)acrylate compound (Y2), a urethane (meth)acrylate compound (Y3), or an aromatic ring-containing (meth)acrylate compound (Y4). As the polymerization initiator, a photopolymerization initiator that generates active radicals upon the action of light is preferred.

[0045] Examples of polymerization initiators include benzoin compounds, benzophenone compounds, alkylphenone compounds, acylphosphine oxide compounds, triazine compounds, iodonium salts, and sulfonium salts. A single polymerization initiator may be used, or two or more may be used in combination.

[0046] Examples of benzoin compounds include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.

[0047] Examples of benzophenone compounds include benzophenone, o-methyl benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, and 2,4,6-trimethylbenzophenone.

[0048] Examples of alkylphenone compounds include diethoxyacetophenone, 2-methyl-2-morpholino-1-(4-methylthiophenyl)propan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butan-1-one, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1,2-diphenyl-2,2-dimethoxyethane-1-one, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]propan-1-one, 1-hydroxycyclohexylphenyl ketone, and oligomers of 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propan-1-one.

[0049] Examples of acylphosphine oxide compounds include 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.

[0050] Examples of triazine compounds include 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxystyryl)-1,3,5-triazine, and 2,4-bis(trichloromethyl)-6-[2-(5-methylfuran-2-yl)ethenyl Examples include triazines such as 2,4-bis(trichloromethyl)-6-[2-(furan-2-yl)ethenyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(4-diethylamino-2-methylphenyl)ethenyl]-1,3,5-triazine, and 2,4-bis(trichloromethyl)-6-[2-(3,4-dimethoxyphenyl)ethenyl]-1,3,5-triazine.

[0051] Commercially available polymerization initiators can also be used. Examples of commercially available polymerization initiators include Irgacure® 907, 184, 651, 819, 250, and 369 (manufactured by Ciba Specialty Chemicals Co., Ltd.); Omnirad 819, Omnirad 907, Esacure 1001M, Esacure KIP160 (manufactured by IDM Resins BV); Seiko Chemicals® BZ, Z, and BEE (manufactured by Seiko Chemicals Ltd.); Kayacure® BP100 and UVI-6992 (manufactured by Dow Chemical Ltd.); Adeka Optomer SP-152 and SP-170 (manufactured by ADEKA Corporation); TAZ-A and TAZ-PP (manufactured by Nippon Siber Hegner Co., Ltd.); and TAZ-104 (manufactured by Sanwa Chemical Co., Ltd.).

[0052] In a preferred embodiment of the present invention, the polymerization initiator used in the resin composition (Y) has a molar extinction coefficient of 10 L·mol at a light source wavelength of 400 nm under acetonitrile solvent. -1 ·cm -1It is preferably at least the above value. A polymerization initiator having such a molar extinction coefficient can generally function as an initiator in the visible light region. This is therefore advantageous when curing the resin composition (Y) through a film that does not transmit light in the ultraviolet region. From the viewpoint of further enhancing the above effect, the molar extinction coefficient of the polymerization initiator at a light source wavelength of 400 nm is more preferably 100 L·mol -1 ·cm -1 or more, preferably 500 L·mol -1 ·cm -1 or more, more preferably 1000 L·mol -1 ·cm -1 or more. In addition, the molar extinction coefficient of the polymerization initiator at a light source wavelength of 400 nm is usually 3000 L·mol -1 ·cm -1 or less. The molar extinction coefficient of the polymerization initiator can be measured, for example, by dissolving the polymerization initiator in acetonitrile to prepare a 0.001% solution, placing the solution in a 1 cm square quartz cell for measurement, and using an ultraviolet-visible spectrophotometer (UV-2450, Shimadzu Corporation).

[0053] When the resin composition (Y) contains a polymerization initiator, the content thereof can be appropriately selected according to the type and amount of the polymerizable compound. From the viewpoint of initiator efficiency, the content is preferably 1 to 10 parts by mass, more preferably 1 to 8 parts by mass, and still more preferably 1 to 5 parts by mass, based on 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y). When the content of the polymerization initiator is within the above range, the curable compound can be sufficiently cured.

[0054] The resin composition (Y) may optionally contain additives such as photosensitizers, leveling agents, polymerization inhibitors, antioxidants, stabilizers, flame retardants, viscosity modifiers, defoamers, and antistatic agents. When the resin composition (Y) contains an additive, the content of the additive is, for example, more than 0% and 10% by mass or less, preferably more than 0% and 5% by mass or less, based on the solid content of the resin composition (Y).

[0055] The viscosity of the resin composition (Y) is preferably 500 mPa·s or less, more preferably 300 mPa·s or less, and even more preferably 250 mPa·s or less at 25°C. When the viscosity of the resin composition (Y) is below the above upper limit, the fluidity of the resin composition (Y) is good, and therefore the resin composition (Y) can be applied uniformly and thinly. The lower limit of the viscosity of the resin composition (Y) at 25°C is usually 5 mPa·s or more. Viscosity can be measured, for example, according to JIS K7117-2.

[0056] The resin layer Y can be formed, for example, by coating a resin composition (Y) onto a surface on which the resin layer Y will be formed, and curing the resin composition (Y) by irradiating the coating with active energy rays. The method of coating the resin composition (Y) and the curing method are not particularly limited and can be appropriately selected from conventionally known general active energy ray curing methods for forming a cured material layer.

[0057] A method for applying the resin composition (Y) is the same as the method for applying the resin composition (X).

[0058] The active energy rays can be appropriately selected depending on the type of curable compound, the type and amount of polymerization initiator, etc. Specific examples of active energy rays include visible light, ultraviolet light, infrared light, X-rays, alpha rays, beta rays, and gamma rays. Among these, ultraviolet light is preferred from the viewpoint of ease of controlling the progress of the polymerization reaction and the fact that photopolymerization equipment widely used in this field can be used.

[0059] Examples of light sources for active energy rays include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, carbon arc lamps, tungsten lamps, gallium lamps, excimer lasers, LED light sources emitting in the wavelength range of 380-440 nm, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps.

[0060] The ultraviolet irradiation intensity is appropriately determined by the composition of the resin composition (Y) and is not particularly limited, but is typically 10 to 3,000 mW / cm². 2 The ultraviolet irradiation intensity is preferably in the wavelength range effective for activating the polymerization initiator. The irradiation time is usually 0.1 seconds to 10 minutes, preferably 1 second to 5 minutes, more preferably 5 seconds to 3 minutes, and even more preferably 10 seconds to 1 minute. When irradiation is performed once or multiple times at such ultraviolet irradiation intensity, the accumulated light amount is 10 to 3,000 mJ / cm². 2 Preferably 50 to 2,000 mJ / cm² 2 More preferably 100-1,000 mJ / cm² 2 That is the case.

[0061] The resin layer Y formed from the above resin composition (Y) preferably contains constituent units derived from a polyfunctional (meth)acrylate compound (Y1), optionally constituent units derived from a hydroxyl group-containing (meth)acrylate compound (Y2), constituent units derived from a urethane (meth)acrylate compound (Y3), and / or constituent units derived from an aromatic ring-containing (meth)acrylate compound (Y4), in amounts or ratios corresponding to the amount of each curable compound blended in the above-described resin composition (Y).

[0062] The thickness of the resin layer Y is not particularly limited and can be appropriately determined depending on the configuration and application of the optical laminate. For example, from the viewpoint of thinning the optical laminate and ensuring adhesion, it is preferably 0.1 to 5 μm, more preferably 0.3 to 4 μm, and even more preferably 0.5 to 3 μm.

[0063] <Polarizing film> The polarizing film includes a cured layer of a polymerizable liquid crystal composition (hereinafter also referred to as the "polarizing film forming composition") containing a polymerizable liquid crystal compound and a dichroic dye. The polarizing film consists of a liquid crystal polarizing film which is the cured layer of the polarizing film forming composition, or the liquid crystal polarizing film and an alignment film for forming the liquid crystal polarizing film. When the polarizing film consists of a liquid crystal polarizing film and an alignment film, the resin layer X may be located on the liquid crystal polarizing film side of the polarizing film, or on the alignment film side. When laminating the resin layer X on the polarizing film, it is common to apply the resin composition (X) to the liquid crystal polarizing film formed on the alignment film to form the resin layer X. For this reason, in one embodiment of the present invention, when the polarizing film consists of a liquid crystal polarizing film and an alignment film, the resin layer X is laminated on the liquid crystal polarizing film side of the polarizing film.

[0064] The liquid crystal polarizing film can be used in organic EL display devices as a circular polarizer with anti-reflective properties when combined with a phase difference film, thereby providing high visibility. When the optical laminate of the present invention functions as a circular polarizer, the liquid crystal polarizing film is typically a horizontal polarizing film in which a polymerizable liquid crystal compound and a dichroic dye are cured in a state in which they are oriented horizontally to the polarizing film plane. Such a horizontal polarizing film typically allows light vibrating in the direction of the transmission axis to pass through, but has the function of blocking the polarization of vibration components perpendicular to it, and functions as a polarizer that extracts linearly polarized light from incident natural light.

[0065] In the present invention, the polymerizable liquid crystal compound (hereinafter also referred to as polymerizable liquid crystal compound (A)) contained in the polarizing film forming composition is a compound having at least one polymerizable group and possessing liquid crystal properties. A photopolymerizable group is preferred as the polymerizable group. This refers to a group that can participate in the polymerization reaction by reaction-active species generated from a photopolymerization initiator, such as active radicals or acids. Examples of photopolymerizable groups include vinyl group, vinyloxy group, 1-chlorovinyl group, isopropenyl group, 4-vinylphenyl group, acryloyloxy group, methacryloyloxy group, oxiranil group, and oxetanyl group. Among these, acryloyloxy group, methacryloyloxy group, vinyloxy group, oxiranil group, and oxetanyl group are preferred, and the acryloyloxy group is more preferred. Polymerizable liquid crystal compound (A) may be used alone or in combination of two or more types.

[0066] In the present invention, the polymerizable liquid crystal compound (A) is preferably a liquid crystal compound exhibiting a smectic liquid crystal phase. By using a polymerizable liquid crystal compound exhibiting a smectic liquid crystal phase, a polarizing film with high orientational order and excellent polarizing function can be formed. From the viewpoint of achieving a higher degree of orientational order, the liquid crystal state exhibited by the polymerizable liquid crystal compound (A) is more preferably a higher-order smectic phase (higher-order smectic liquid crystal state). Here, the higher-order smectic phase refers to smectic B phase, smectic D phase, smectic E phase, smectic F phase, smectic G phase, smectic H phase, smectic I phase, smectic J phase, smectic K phase, and smectic L phase, and among these, smectic B phase, smectic F phase, and smectic I phase are more preferred. The liquid crystalline properties can be either thermotropic or lyotropic, but thermotropic liquid crystalline properties are preferred due to their miscibility with dichroic dyes (described later) and the ability to precisely control film thickness. Furthermore, the polymerizable liquid crystal compound (A) may be a monomer, an oligomer formed by polymerization of polymerizable groups, or a polymer.

[0067] Examples of such polymerizable liquid crystal compounds (A) include the compound represented by formula (A1) (hereinafter also referred to as "polymerizable liquid crystal compound (A1)"). U 1 -V 1 -W 1 -(X 1 -Y 1 ) n -X 2 -W 2 -V 2 -U 2 (A1)

[0068] In formula (A1), X 1 and X 2 Each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group, where the hydrogen atoms in the divalent aromatic group or divalent alicyclic hydrocarbon group may be substituted with halogen atoms, C1-C4 alkyl groups, C1-C4 fluoroalkyl groups, C1-C4 alkoxy groups, cyano groups, and nitro groups, and the carbon atoms constituting the divalent aromatic group or divalent alicyclic hydrocarbon group may be substituted with oxygen atoms, sulfur atoms, or nitrogen atoms. However, X 1 and X 2 At least one of these is a 1,4-phenylene group which may have the above substituent, or a cyclohexane-1,4-diyl group which may have the above substituent. Y 1 It is a single bond or a divalent linking group. n is 1 to 3, and if n is 2 or greater, multiple X 1 They may be the same or they may be different. 2 is multiple X 1 It may be the same as or different from any or all of the following. Also, if n is 2 or more, there may be multiple Y 1 These values ​​may be the same or different. From the viewpoint of liquid crystalline properties, n is preferably 2 or greater. U 1 represents a hydrogen atom or a polymerizable group. U 2 This represents a polymerizable group. W 1 and W 2 These are, independently of each other, single or divalent linking groups. V1 and V 2 Each of these independently represents an alkanediyl group having 1 to 20 carbon atoms, which may have substituents, and the -CH2- constituting the alkanediyl group may be replaced with -O-, -CO-, -S-, or -NH-.

[0069] In polymerizable liquid crystal compound (A1), X 1 and X 2 These are, independently of each other, preferably a substituted 1,4-phenylene group or a substituted cyclohexane-1,4-diyl group, and X 1 and X 2 At least one of these is an optionally substituted 1,4-phenylene group or an optionally substituted cyclohexane-1,4-diyl group, preferably a trans-cyclohexane-1,4-diyl group. Optional substituents on the optionally substituted 1,4-phenylene group or the optionally substituted cyclohexane-1,4-diyl group include C1-C4 alkyl groups such as methyl, ethyl, and butyl groups, cyano groups, and halogen atoms such as chlorine and fluorine atoms. It is preferably unsubstituted.

[0070] Furthermore, polymerizable liquid crystal compound (A1) is a compound of formula (A1-1): -(X 1 -Y 1 ) n -X 2 - (A1-1) [In the formula, X 1 , Y 1 , X 2 And n have the same meaning as above. The fact that the portion indicated by [hereinafter referred to as substructure (A1-1)] has an asymmetric structure is preferable because it easily exhibits smectic liquid crystal properties. Examples of polymerizable liquid crystal compounds (A) whose substructure (A1-1) is asymmetric include: n is 1 and one X 1 and X 2A polymerizable liquid crystal compound (A1) in which the two have different structures is also an example. 1 Compounds in which two X have the same structure 1 They have the same structure as each other, and one X 2 These two X 1 Polymerizable liquid crystal compound (A1) has a different structure from two X 1 W 1 X that binds 1 However, the other X 1 and X 2 It has a different structure, and the other X 1 and X 2 Another example is the polymerizable liquid crystal compound (A1) which has the same structure as the others. Furthermore, n is 3, and there are three Y 1 Compounds in which the three X's are identical in structure 1 and one X 2 A polymerizable liquid crystal compound (A1) is one in which one of the structures is different from all three others.

[0071] Y 1 -CH2CH2-, -CH2O-, -CH2CH2O-, -COO-, -OCOO-, single bond, -N=N-, -CR a =CR b -, -C≡C-, -CR a =N- or -CO-NR a - is preferable. a and R b Each of these independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. 1 It is more preferably -CH2CH2-, -COO-, or a single bond, and multiple Y 1 If X 2 Y that combines with 1 It is more preferable that it be -CH2CH2- or -CH2O-. 1 and X 2 If all have the same structure, then two or more Y have different bonding methods. 1 It is preferable that multiple Ys with different coupling methods exist. 1When present, the structure becomes asymmetric, which tends to facilitate the exhibition of smectic liquid crystallinity.

[0072] U 2 is a polymerizable group. U 1 is a hydrogen atom or a polymerizable group, and is preferably a polymerizable group. U 1 and U 2 are preferably both polymerizable groups, and are more preferably both radical polymerizable groups. Examples of the polymerizable group include the same groups as those previously exemplified as the polymerizable group that the polymerizable liquid crystal compound (A) has. U 1 The polymerizable group represented by and U 2 The polymerizable group represented by may be different from each other, but are preferably groups of the same type. In addition, the polymerizable group may be in a polymerized state or in an unpolymerized state, and is preferably in an unpolymerized state.

[0073] V 1 and V 2 Examples of the alkanediyl group represented by include a methylene group, ethylene group, propane-1,3-diyl group, butane-1,3-diyl group, butane-1,4-diyl group, pentane-1,5-diyl group, hexane-1,6-diyl group, heptane-1,7-diyl group, octane-1,8-diyl group, decane-1,10-diyl group, tetradecane-1,14-diyl group, icosane-1,20-diyl group and the like. V 1 and V 2 are preferably alkanediyl groups having 2 to 12 carbon atoms, and more preferably alkanediyl groups having 6 to 12 carbon atoms.

[0074] Examples of the substituent that the alkanediyl group optionally has include a cyano group, a halogen atom and the like, and the alkanediyl group is preferably unsubstituted, and more preferably an unsubstituted linear alkanediyl group.

[0075] W 1 and W 2These are preferably single bonds, -O-, -S-, -COO-, or -OCOO-, and more preferably single bonds or -O-.

[0076] A structure that readily exhibits smectic liquid crystal properties is preferably one that has an asymmetric molecular structure. Specifically, polymerizable liquid crystal compounds having the structures shown by formulas (Aa) to (Ai) below readily exhibit smectic liquid crystal properties and are suitable as polymerizable liquid crystal compound (A). Furthermore, from the viewpoint of readily exhibiting higher-order smectic liquid crystal properties, it is more preferable to have the structures shown by formulas (Aa), (Ab), or (Ac). In formulas (Aa) to (Ai) below, * represents a bond (single bond).

[0077] [ka]

[0078] Examples of polymerizable liquid crystal compounds (A) include those represented by formulas (A-1) to (A-25). When polymerizable liquid crystal compound (A) has a cyclohexane-1,4-diyl group, it is preferable that the cyclohexane-1,4-diyl group is in trans form.

[0079] [ka]

[0080] [ka]

[0081] [ka]

[0082] Among these, at least one selected from the group consisting of compounds represented by formulas (A-2), (A-3), (A-4), (A-5), (A-6), (A-7), (A-8), (A-13), (A-14), (A-15), (A-16), and (A-17) is preferred. As the polymerizable liquid crystal compound (A1), one type may be used alone, or two or more types may be used in combination.

[0083] Polymerizable liquid crystal compound (A1) can be produced by known methods described in Lub et al., Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996), or Japanese Patent No. 4719156, etc.

[0084] The polarizing film-forming composition may contain polymerizable liquid crystal compounds other than polymerizable liquid crystal compound (A1), but from the viewpoint of obtaining a polarizing film with a high degree of orientation order, the ratio of polymerizable liquid crystal compound (A1) to the total mass of all polymerizable liquid crystal compounds in the polarizing film-forming composition is preferably 51% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more of polymerizable liquid crystal compounds are polymerizable liquid crystal compound (A1), and may be entirely (100% by mass) polymerizable liquid crystal compound (A1).

[0085] When the polarizing film-forming composition contains two or more polymerizable liquid crystal compounds, it is preferable that at least one of them is polymerizable liquid crystal compound (A1), and it is also possible that all of the components in the polarizing film-forming composition are polymerizable liquid crystal compounds (A1).

[0086] The content of polymerizable liquid crystal compound (A) in the polarizing film-forming composition is preferably 40 to 99.9% by mass, more preferably 60 to 99.9% by mass, and even more preferably 70 to 99% by mass, relative to the solid content of the polarizing film-forming composition. When the content of polymerizable liquid crystal compound (A) is within the above range, the orientation of the polymerizable liquid crystal compound tends to be high.

[0087] The composition for forming a polarizing film contains a dichroic dye. Here, the dichroic dye means a dye having a property that the absorbance in the major axis direction of the molecule differs from the absorbance in the minor axis direction. The dichroic dye that can be used in the present invention is not particularly limited as long as it has the above property, and may be a dye or a pigment. Two or more kinds of dyes or pigments may be used in combination respectively, or a dye and a pigment may be used in combination. The dichroic dyes may be used alone or in combination, but in order to obtain absorption over the entire visible light region, it is preferable to combine two or more kinds of dichroic dyes, and it is more preferable to combine three or more kinds of dichroic dyes. In particular, by mixing two or more kinds of dichroic dyes having different absorption wavelengths, polarizing films of various hues can be produced, and a polarizing film having absorption over the entire visible light region can be obtained.

[0088] The dichroic dye preferably has a property of absorbing visible light, and preferably has a maximum absorption wavelength (λ in the range of 300 to 700 nm MAX ). Examples of such dichroic dyes include acridine dyes, oxazine dyes, cyanine dyes, naphthalene dyes, azo dyes, anthraquinone dyes and the like. Among them, azo dyes are preferred.

[0089] Examples of the azo dyes include monoazo dyes, bisazo dyes, trisazo dyes, tetrakisazo dyes, stilbene azo dyes and the like, and bisazo dyes and trisazo dyes are preferred, and examples thereof include the compound represented by the formula (I) (hereinafter also referred to as "compound (I)").

[0090] K 1 (-N=N-K 2 ) p -N=N-K 3 (I) In the formula (I), K 1 and K 3 each independently represent a phenyl group which may have a substituent, a naphthyl group which may have a substituent, a benzoic acid phenyl ester group which may have a substituent, or a monovalent heterocyclic group which may have a substituent. K 2k represents an optionally substituted p-phenylene group, an optionally substituted naphthalene-1,4-diyl group, an optionally substituted 4,4'-stilbenylene group, or an optionally substituted divalent heterocyclic group. p represents an integer from 0 to 4. If p is an integer of 2 or more, multiple k 2 These may be identical or different from each other. Within the range showing absorption in the visible spectrum, the -N=N- bond may be replaced by -C=C-, -COO-, -NHCO-, or -N=CH- bonds.

[0091] Examples of monovalent heterocyclic groups include groups obtained by removing one hydrogen atom from heterocyclic compounds such as quinoline, thiazole, benzothiazole, thienothiazole, imidazole, benzimidazole, oxazole, and benzoxazole. Examples of divalent heterocyclic groups include groups obtained by removing two hydrogen atoms from the aforementioned heterocyclic compounds.

[0092] K 1 and K 3 The phenyl group, naphthyl group, phenyl benzoate ester group and monovalent heterocyclic group in, and K 2 The p-phenylene group, naphthalene-1,4-diyl group, 4,4'-stilbenylene group, and divalent heterocyclic group may optionally have substituents such as C1-C20 alkyl groups, C1-C20 alkyl groups with polymerizable groups, C1-C4 alkenyl groups; C1-C20 alkoxy groups such as methoxy, ethoxy, and butoxy groups; C1-C20 alkoxy groups with polymerizable groups; C1-C4 fluorinated alkyl groups such as trifluoromethyl groups; and Examples include ano groups; nitro groups; halogen atoms; substituted or unsubstituted amino groups such as amino groups, diethylamino groups, and pyrrolidino groups (a substituted amino group means an amino group having one or two C1-C6 alkyl groups, an amino group having one or two C1-C6 alkyl groups that have a polymerizable group, or an amino group in which two substituted alkyl groups are bonded to each other to form an alkanediyl group having 2-C8. An unsubstituted amino group is -NH2). Examples of polymerizable groups include (meth)acryloyl groups and (meth)acryloyloxy groups.

[0093] Among the compounds (I), compounds represented by any of the following formulas (I-1) to (I-8) are preferred. [ka] [In equations (I-1) to (I-8), B 1 ~B 30 These independently represent a hydrogen atom, a C1-C6 alkyl group, a C1-C6 alkenyl group, a C1-C4 alkoxy group, a cyano group, a nitro group, a substituted or unsubstituted amino group (as defined above), a chlorine atom, or a trifluoromethyl group. n1 to n4 represent integers from 0 to 3, independently of each other. If n1 is 2 or more, multiple B 2 They may be the same or different from each other. If n2 is 2 or more, multiple B 6 They may be the same or different from each other. If n3 is 2 or more, multiple B 9 They may be the same or different from each other. If n4 is 2 or more, multiple B 14 They may be the same or different from each other.

[0094] As the anthraquinone dye, compounds represented by formula (I-9) are preferred. [ka] [In formula (I-9), R 1 ~R 8 These are, independently of each other, hydrogen atoms, -R x -NH2, -NHR x , -NR x 2, -SR x Alternatively, it represents a halogen atom. R x This represents an alkyl group with 1 to 4 carbon atoms or an aryl group with 6 to 12 carbon atoms.

[0095] As the oxazone dye, a compound represented by formula (I-10) is preferred. [ka] [In formula (I-10), R 9 ~R 15 These are, independently of each other, hydrogen atoms, -R x -NH2, -NHR x , -NR x 2, -SR x Alternatively, it represents a halogen atom. R x This represents an alkyl group with 1 to 4 carbon atoms or an aryl group with 6 to 12 carbon atoms.

[0096] As the acridine dye, a compound represented by formula (I-11) is preferred. [ka] [In formula (I-11), R 16 ~R 23 These are, independently of each other, hydrogen atoms, -R x -NH2, -NHR x , -NR x 2, -SR x Alternatively, it represents a halogen atom. R x This represents an alkyl group with 1 to 4 carbon atoms or an aryl group with 6 to 12 carbon atoms. In equations (I-9), (I-10), and (I-11), R x Examples of alkyl groups having 1 to 6 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, and hexyl groups, while examples of aryl groups having 6 to 12 carbon atoms include phenyl, toluyl, xylyl, and naphthyl groups.

[0097] As the cyanine dye, compounds represented by formula (I-12) and compounds represented by formula (I-13) are preferred. [ka] [In formula (I-12), D 1 and D 2 These represent, independently of each other, a base expressed by any of the formulas (I-12a) to (I-12d). [ka] n5 represents an integer between 1 and 3. [ka] [In formula (I-13), D 3 and D 4 These represent, independently of each other, a base expressed by any of the formulas (1-13a) to (1-13h). [ka] n6 represents an integer between 1 and 3.

[0098] The weight-average molecular weight of dichroic dyes is typically 300 to 2000, preferably 400 to 1000.

[0099] The content of the dichroic dye in the polarizing film-forming composition can be appropriately determined depending on the type of dichroic dye used, but is preferably 1 to 60% by mass, more preferably 1 to 20% by mass, and even more preferably 1 to 15% by mass, relative to the solid content of the polarizing film-forming composition. When the content of the dichroic dye is within the above range, it is less likely to disrupt the orientation of the polymerizable liquid crystal compound, and a polarizing film with a high degree of orientation order can be obtained.

[0100] The polarizing film-forming composition may contain a polymerization initiator. As the polymerization initiator, a photopolymerization initiator that generates active radicals or acids upon the action of light is preferred, and a photopolymerization initiator that generates radicals upon the action of light is more preferred, as it allows the polymerization reaction to be initiated under lower temperature conditions. The polymerization initiator may be used alone or in combination of two or more types.

[0101] As the photopolymerization initiator, known photopolymerization initiators can be used. For example, those similar to those exemplified above can be used in the resin composition (Y), and they should be appropriately selected in relation to the polymerizable liquid crystal compound that forms the polarizing film.

[0102] The content of the polymerization initiator is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 15 parts by mass, even more preferably 0.5 to 10 parts by mass, and particularly preferably 0.5 to 8 parts by mass, per 100 parts by mass of polymerizable liquid crystal compound (A) in the polarizing film forming composition. When the content of the polymerization initiator is within the above range, the polymerization reaction can be carried out without significantly disrupting the orientation of the polymerizable liquid crystal compound.

[0103] The polarizing film-forming composition may contain a leveling agent. The leveling agent has the function of adjusting the fluidity of the polarizing film-forming composition and making the coating obtained by applying the composition flatter. Specifically, surfactants are examples. As the leveling agent, at least one selected from the group consisting of leveling agents mainly composed of polyacrylate compounds and leveling agents mainly composed of fluorine atom-containing compounds is preferred. Leveling agents can be used alone or in combination of two or more types.

[0104] Examples of leveling agents primarily composed of polyacrylate compounds include BYK-350, BYK-352, BYK-353, BYK-354, BYK-355, BYK-358N, BYK-361N, BYK-380, BYK-381, and BYK-392 (BYK Chemie).

[0105] Examples of leveling agents whose main component is a fluorine atom-containing compound include Megafac® R-08, R-30, R-90, F-410, F-411, F-443, F-445, F-470, F-471, F-477, F-479, F-482, F-483 and F-556 (DIC Corporation); Surflon® S-381, S-382, S-383, S-393, SC-101, SC-105, KH-40 and SA-100 (AGC Seimi Chemical Co., Ltd.); E1830, E5844 (Daikin Fine Chemical Laboratories, Inc.); F-Top EF301, F-Top EF303, F-Top EF351 and F-Top EF352 (Mitsubishi Materials Electronic Chemicals Co., Ltd.).

[0106] When the polarizing film-forming composition contains a leveling agent, its content is preferably 0.01 to 5 parts by mass, and more preferably 0.05 to 3 parts by mass, per 100 parts by mass of the polymerizable liquid crystal compound (A) contained in the polarizing film-forming composition. When the leveling agent content is within the above range, the polymerizable liquid crystal compound is easily oriented, unevenness is less likely to occur, and a smoother liquid crystal polarizing film can be obtained.

[0107] The polarizing film-forming composition may contain additives other than leveling agents. Examples of other additives include ionic compounds, photosensitizers, antioxidants, mold release agents, stabilizers, colorants such as bluing agents, flame retardants, and lubricants. When other additives are included, the content of the other additives is preferably more than 0% and 20% by mass or less, and more preferably more than 0% and 10% by mass or less, relative to the solid content of the polarizing film-forming composition.

[0108] The polarizing film-forming composition may contain a solvent. Adding a solvent to the polarizing film-forming composition often facilitates application, resulting in easier formation of the polarizing film. In particular, compounds that generally exhibit smectic liquid crystal properties have high viscosity, so including a solvent is advantageous in terms of application and handling. The solvent can be appropriately selected depending on the solubility of the polymerizable liquid crystal compound (A) and the dichroic dye. Examples include alcohol solvents such as water, methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, methyl amyl ketone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; and chlorinated hydrocarbon solvents such as chloroform and chlorobenzene. These solvents can be used individually or in combination of two or more.

[0109] The polarizing film-forming composition can be prepared by conventionally known liquid crystal composition preparation methods, and is typically prepared by mixing and stirring a polymerizable liquid crystal compound (A), a dichroic dye, and optionally a polymerization initiator, solvent, and the above-mentioned additives.

[0110] A liquid crystal polarizing film is formed, for example, by forming a coating film of a polarizing film-forming composition. Removing the solvent from the aforementioned coating film, The polymerizable liquid crystal compound (A) is heated to a temperature above the temperature at which it undergoes a phase transition to the liquid phase, and then cooled to cause the polymerizable liquid crystal compound (A) to undergo a phase transition to the liquid crystal phase (e.g., smectic liquid crystal phase), and Polymerizing the polymerizable liquid crystal compound (A) while retaining the liquid crystal phase. It can be manufactured by a method that includes [a specific component].

[0111] The polarizing film-forming composition can be formed by coating it onto a substrate or an alignment film (described later). The substrate can be a layer constituting the optical laminate of the present invention, but in one embodiment of the present invention, it is preferable that it is ultimately peeled off. As the substrate, a resin film substrate or the like, which is conventionally known in the field of optical films, can be used. The film substrate may be subjected to surface treatments such as corona treatment or plasma treatment, and if the substrate is to be peeled off later, a release treatment may be applied. The thickness of the substrate is not particularly limited and can be appropriately selected within a practical range. For example, it may be about 5 to 300 μm.

[0112] The method for applying the polarizing film-forming composition to a substrate or the like, and the method for removing the solvent are not particularly limited, and the same methods as those exemplified above can be used for producing resin layers X and B.

[0113] The polymerizable liquid crystal compound (A) in the coating film is typically heated above the temperature at which it transitions to a liquid crystal state or solution state, and then cooled to the temperature at which it aligns, thereby aligning and forming a liquid crystal phase. The temperature at which the polymerizable liquid crystal compound (A) in the coating film aligns can be determined in advance by observing the texture of a composition containing the polymerizable liquid crystal compound (A). Alternatively, solvent removal and liquid crystal alignment may be performed simultaneously. The temperature for this process depends on the solvent to be removed and the type of polymerizable liquid crystal compound used, but is preferably in the range of 50 to 200°C, and more preferably in the range of 80 to 130°C.

[0114] By polymerizing the polymerizable liquid crystal compound (A) while maintaining its liquid crystal state, a cured film of the polymerizable liquid crystal composition is formed as a liquid crystal polarizing film. Photopolymerization is preferred as the polymerization method. In photopolymerization, the light irradiated onto the dried coating film is appropriately selected according to the type of polymerization initiator contained in the dried coating film, the type of polymerizable liquid crystal compound (A) (particularly the type of polymerizable group possessed by the polymerizable liquid crystal compound), and its amount. Specific examples of the irradiation light and its light source are the same as those previously exemplified in the method for producing the resin layer Y. The irradiation intensity of the light (ultraviolet light) is appropriately selected according to the composition of the polarizing film forming composition, the thickness of the liquid crystal polarizing film, the light source, etc., and for example, the same as those previously exemplified in the method for producing the resin layer Y can be used.

[0115] By photopolymerization, the polymerizable liquid crystal compound (A) polymerizes while maintaining a liquid crystal state, preferably a smectic phase, more preferably a higher-order smectic phase, thereby forming a liquid crystal polarizing film. The liquid crystal polarizing film obtained by polymerizing the polymerizable liquid crystal compound (A) while maintaining a liquid crystal state of the smectic phase has the advantage of higher polarization performance compared to conventional host-guest type polarizing films, i.e., polarizing films consisting of a liquid crystal state of the nematic phase.

[0116] The thickness of the liquid crystal polarizing film can be appropriately selected depending on the display device to which it is applied, and is preferably 0.1 to 10 μm, more preferably 0.3 to 4 μm, and even more preferably 0.5 to 3 μm.

[0117] In the present invention, the liquid crystal polarizing film is preferably a liquid crystal polarizing film with a high degree of orientation order. A liquid crystal polarizing film with a high degree of orientation order yields Bragg peaks originating from higher-order structures such as the hexatic phase and the crystalline phase in X-ray diffraction measurements. A Bragg peak refers to a peak originating from the periodic plane structure of molecular orientation. Therefore, it is preferable that the liquid crystal polarizing film constituting the optical laminate of the present invention exhibits a Bragg peak in X-ray diffraction measurements. That is, in the present invention, it is preferable that the polymerizable liquid crystal compound or its polymer is oriented such that the film exhibits a Bragg peak in X-ray diffraction measurements. In one embodiment of the present invention, it is preferable that the periodic plane spacing of the molecular orientation is 3.0 to 6.0 Å. A high degree of orientation order that exhibits a Bragg peak can be achieved by controlling the type of polymerizable liquid crystal compound used, the type and amount of dichroic dye, and the type and amount of polymerization initiator.

[0118] In the present invention, a liquid crystal polarizing film can be formed on an alignment film. The alignment film for forming the liquid crystal polarizing film has an orientation-regulating force that causes the polymerizable liquid crystal compound (A) to be liquid crystal-aligned in a desired direction, and a liquid crystal polarizing film with high precision can be easily obtained by applying a polarizing film-forming composition onto the alignment film. The alignment film is preferably solvent-resistant, not dissolved by the application of the polarizing film-forming composition, and also has heat resistance for solvent removal and heat treatment for the orientation of the polymerizable liquid crystal compound.

[0119] Examples of orientation films include orientation films containing orientation polymers, photo-alignment films, groove-alignment films having surface irregularities or multiple grooves, and stretched films stretched in the orientation direction. These various orientation films can be appropriately selected from those conventionally known in the field, depending on the desired orientation restricting force.

[0120] In one embodiment of the present invention, from the viewpoint of easily improving alignment accuracy and adhesion with the liquid crystal polarizing film, it is preferable that the polarizing film includes a photo-alignment film, that is, that the liquid crystal polarizing film is formed on the photo-alignment film. The photo-alignment film is also advantageous in that the direction of the alignment restricting force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.

[0121] Photo-alignment films are typically obtained by coating a composition containing a polymer, oligomer, or monomer having a photoreactive group and a solvent (hereinafter also referred to as a "photo-alignment film forming composition") onto a substrate or the like, and irradiating it with polarized light (preferably polarized UV). A photoreactive group is a group that generates liquid crystal alignment ability upon light irradiation. Specifically, this includes groups involved in photoreactions that are the origin of liquid crystal alignment ability, such as molecular orientation induction or isomerization reactions, dimerization reactions, photocrosslinking reactions, or photodegradation reactions caused by light irradiation. Among these, groups involved in dimerization reactions or photocrosslinking reactions are preferred in that they have excellent alignment properties. As photoreactive groups, groups having unsaturated bonds, especially double bonds, are preferred, and groups having at least one selected from the group consisting of carbon-carbon double bonds (C=C bonds), carbon-nitrogen double bonds (C=N bonds), nitrogen-nitrogen double bonds (N=N bonds), and carbon-oxygen double bonds (C=O bonds) are particularly preferred.

[0122] Examples of photoreactive groups having a C=C bond include vinyl groups, polyene groups, stilbene groups, stilbazole groups, stilbazolium groups, chalcone groups, and cinnamoyl groups. Examples of photoreactive groups having a C=N bond include groups having structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups having an N=N bond include azobenzene groups, azonaphthalene groups, aromatic heterocyclic azo groups, bisazo groups, formazan groups, and groups having an azoxybenzene structure. Examples of photoreactive groups having a C=O bond include benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups. These groups may have substituents such as alkyl groups, alkoxy groups, allyl groups, allyloxy groups, cyano groups, alkoxycarbonyl groups, hydroxyl groups, sulfonic acid groups, and halogenated alkyl groups.

[0123] Among these, photoreactive groups involved in the photodimerization reaction are preferred, and cinnamoyl groups and chalcone groups are preferred because they require a relatively small amount of polarized irradiation for photo-orientation, and it is easy to obtain a photo-orientation film with excellent thermal stability and chronological stability. As for polymers having photoreactive groups, those having cinnamoyl groups such that the terminal portion of the polymer side chain has a cinnamic acid structure are particularly preferred. Furthermore, from the viewpoint of adhesion to adjacent layers, it is preferable that the polymer, oligomer, or monomer having photoreactive groups has (meth)acrylic groups, and (meth)acrylic oligomers or polymers having cinnamoyl groups such that the terminal portion of the oligomer or polymer side chain has a cinnamic acid structure are preferred.

[0124] Photo-alignment films can be formed by conventionally known methods for producing photo-alignment films. Specifically, for example, a photo-alignment film can be formed by applying a photo-alignment film forming composition onto a substrate to form a photo-alignment induction layer, and then irradiating the photo-alignment induction layer, from which the solvent has been removed, with polarized light.

[0125] Examples of such photo-alignment films include those described in Japanese Patent Publication No. 2021-196514 and International Publication No. 2018 / 003416.

[0126] The thickness of the orientation film is typically 10 to 5000 nm, preferably 10 to 1000 nm, more preferably 10 to 500 nm, even more preferably 10 to 300 nm, and particularly preferably 30 to 300 nm.

[0127] In one embodiment of the present invention, the optical laminate of the present invention includes a phase difference film adjacent to the resin layer Y on the side opposite to the resin layer X. The optical laminate of the present invention, in which a polarizing film, resin layer X, and resin layer Y are adjacent in this order, can also achieve high adhesion of the resin layer Y to the adjacent layer on the side opposite to the resin layer X. Therefore, when a phase difference film is adjacent to the resin layer Y on the side opposite to the resin layer X, it is possible to provide an optical laminate (circular polarizer) that has excellent durability in high temperature and high humidity environments, as well as excellent adhesion between the polarizing film and the phase difference film. In the present invention, the phase difference film includes a cured layer of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound (hereinafter also referred to as "phase difference film forming composition"). The phase difference film consists of a cured layer of the phase difference film forming composition (hereinafter also referred to as "liquid crystal phase difference film"), or consists of the liquid crystal phase difference film and an alignment film for forming the liquid crystal phase difference film. When the phase difference film consists of a liquid crystal phase difference film and an alignment film, the resin layer Y may be located on the liquid crystal phase difference film side of the phase difference film, or on the alignment film side. In one embodiment of the present invention, when the phase difference film consists of a liquid crystal phase difference film and an alignment film, the alignment film is located on the resin layer Y side.

[0128] When the optical laminate of the present invention includes a phase difference film adjacent to the resin layer Y on the opposite side of the resin layer X, and the in-plane average refractive index of the resin layer X is n1, the in-plane average refractive index of the resin layer Y is n2, and the in-plane average refractive index of the phase difference film is n3, then the following equation (2): |(n1×n3) 1 / 2 -n²| ≤ 0.05 (2) It is preferable that the following conditions are met. When the average in-plane refractive index of these three layers satisfies the above relationship, it is expected that light reflection at the interface between two adjacent layers can be suppressed. As a result, when the resulting optical laminate is incorporated into a display device, light reflection between each layer of incoming ambient light can be effectively suppressed, improving the visibility of the image display panel. To further enhance this effect, |(n1×n3) 1 / 2 The value of -n2| is more preferably 0.04 or less, even more preferably 0.035 or less, and particularly preferably 0.03 or less. |(n1×n3) 1 / 2The closer the value of -n2| is to 0, the smaller the difference in refractive index between the layers. Its lower limit can be 0, but it may also be, for example, 0.0001 or greater, or 0.001 or greater. When the phase difference film consists of a liquid crystal phase difference film and an alignment film, the in-plane average refractive index n3 refers to the in-plane average refractive index measured with the liquid crystal phase difference film and the alignment film together.

[0129] |(n1×n3) in equation (2) 1 / 2 The value of -n2| can be controlled by the types of components constituting the resin layer X, resin layer Y, and phase difference film, their combinations, and their blending ratios.

[0130] In one embodiment of the optical laminate of the present invention, in which a phase difference film is laminated adjacent to the resin layer Y on the opposite side of the resin layer X, the in-plane average refractive index n2 of the resin layer Y is preferably 1.45 to 1.60, more preferably 1.50 to 1.57. When the in-plane average refractive index n2 of the resin layer Y is within the above range, light reflection at the interface between the resin layer X and the resin layer Y can be suppressed. Furthermore, light reflection at the interface between the resin layer Y and the phase difference film can also be suppressed. As a result, when the resulting optical laminate is incorporated into a display device, it has an excellent effect in suppressing light reflection between two adjacent layers. The in-plane average refractive index of the resin layer Y can be controlled by the type of components constituting the resin layer Y, their combination, etc.

[0131] In the above embodiment of the present invention, the in-plane average refractive index n1 of the resin layer X is preferably 1.40 to 1.60, more preferably 1.43 to 1.50. When the in-plane average refractive index n1 of the resin layer X is within the above range, the light reflection suppression effect at the interface with the resin layer Y is easily enhanced. The in-plane average refractive index of the resin layer X can be controlled by the type of components constituting the resin layer X, their combination, etc.

[0132] Furthermore, in the above embodiment of the present invention, the in-plane average refractive index n3 of the phase difference film is preferably 1.50 to 1.70, more preferably 1.55 to 1.65. When the in-plane average refractive index n3 of the phase difference film is within the above range, the light reflection suppression effect at the interface with the resin layer Y is easily enhanced. The in-plane average refractive index of the phase difference film can be controlled by the type of polymerizable liquid crystal compound constituting the phase difference film, its combination, etc.

[0133] In the present invention, the in-plane average refractive indices of the resin layer X, resin layer Y, and phase difference film are the refractive indices at a wavelength of 589 nm, and can be measured using an Abbe refractometer or a KOBRA-WR (manufactured by Oji Instruments Co., Ltd.). Specifically, they can be measured, for example, according to the method described in the examples below.

[0134] In the present invention, the liquid crystal phase difference film can be formed by polymerizing a polymerizable liquid crystal compound (hereinafter also referred to as "polymerizable liquid crystal compound (B)") contained in the phase difference film forming composition, and is a film cured in a state in which the polymerizable liquid crystal compound is oriented. For the optical laminate of the present invention to function as a circular polarizer, it is preferable to include a liquid crystal phase difference film having a λ / 4 wave plate function (i.e., a π / 2 phase difference function) as the liquid crystal phase difference film. If the liquid crystal phase difference film has a λ / 4 wave plate function over the entire visible light range, a high level of anti-reflection function can be achieved. A liquid crystal phase difference film having a λ / 4 wave plate function may be, for example, a "horizontally oriented liquid crystal cured film" in which the polymerizable liquid crystal compound (B) is cured in a state in which it is oriented horizontally with respect to the phase difference film plane. In this case, if the polymerizable liquid crystal compound (B) is a rod-shaped liquid crystal, it may be a positive A plate, and if the polymerizable liquid crystal compound (B) is a disc-shaped liquid crystal, it may be a negative A plate.

[0135] The optical laminate of the present invention preferably includes a liquid crystal phase difference film that satisfies the optical properties shown in the following formula (3) when the in-plane phase difference value with respect to light of wavelength λnm is R(λ). In one embodiment of the present invention, it is more preferable to include a liquid crystal phase difference film that satisfies the optical properties shown in the following formulas (3), (4), and (5). 100nm <Re(550)<170nm (3) (In the formula, Re(550) represents the in-plane phase difference value (in-plane retardation) for light with a wavelength of 550 nm.) Re(450) / Re(550)≦1.0 (4) 1.00 ≤ Re(650) / Re(550) (5) (In the formula, Re(450) represents the in-plane phase difference value for light with a wavelength of 450 nm, Re(550) represents the in-plane phase difference value for light with a wavelength of 550 nm, and Re(650) represents the in-plane phase difference value for light with a wavelength of 650 nm.)

[0136] If the in-plane phase difference value Re(550) of the liquid crystal phase difference film is within the range of equation (3), the phase difference film functions as a λ / 4 wave plate, and the effect of improving the front reflected hue (effect of suppressing coloration) when an optical laminate (circular polarizer) containing the phase difference film is applied to an organic EL display device, etc., is enhanced. Furthermore, if the liquid crystal phase difference film satisfies the above equations (4) and (5), it exhibits so-called inverse wavelength dispersion, where the in-plane phase difference value at short wavelengths is smaller than the in-plane phase difference value at long wavelengths. An optical laminate (circular polarizer) having such a liquid crystal phase difference film has an excellent effect of suppressing light leakage on the short wavelength side and tends to have excellent front hue when incorporated into an organic EL display device, etc. From the viewpoint of improving inverse wavelength dispersion and further enhancing the effect of improving the reflected hue in the front direction, Re(450) / Re(550) is preferably 0.7 to 1.0, more preferably 0.80 to 0.95, even more preferably 0.80 to 0.92, and particularly preferably 0.82 to 0.88. Also, Re(650) / Re(550) is preferably 1.01 or higher, more preferably 1.02 or higher. These values ​​can be arbitrarily controlled by adjusting the mixing ratio of polymerizable liquid crystal compound (B) and the stacking angle and phase difference value of the multiple phase difference films.

[0137] The in-plane retardation value can be adjusted by the film thickness d of the liquid crystal retardation film. The in-plane retardation value is determined by the formula Re(λ)=(nx(λ)-ny(λ))×d [wherein nx(λ) represents the main refractive index at a wavelength of λ nm in the plane of the liquid crystal retardation film, ny(λ) represents the refractive index at a wavelength of λ nm in the direction orthogonal to the direction of nx in the same plane as nx, and d represents the film thickness of the liquid crystal retardation film]. Therefore, in order to obtain a desired in-plane retardation value (Re(λ): the in-plane retardation value of the retardation film at a wavelength of λ (nm)), the three-dimensional refractive index and the film thickness d may be adjusted.

[0138] In the optical laminate of the present invention, the number of retardation films may be one, or two or more. Specifically, it is preferable to include a retardation film having a λ / 4 wavelength plate function, particularly a retardation film having a reverse wavelength dispersion λ / 4 wavelength plate function, or it is preferable to combine two or more types of retardation films with different orientations. For example, a combination of a retardation film having a λ / 2 wavelength plate function (that is, a π retardation function) and a retardation film having a λ / 4 wavelength plate function (that is, a π / 2 retardation function) may be used. Further, for example, in addition to the retardation film having a λ / 4 wavelength plate function, a retardation film that is a positive C-plate (nx≈ny<nz) may be included. The liquid crystal retardation film that is a positive C-plate is usually a "vertically aligned liquid crystal cured film" obtained by curing the polymerizable liquid crystal compound (B) in a state of being aligned in the direction perpendicular to the plane of the retardation film. By including a combination of a retardation film having a 1 / 4 wavelength plate function and a retardation film that is a positive C-plate, when the optical laminate is applied to an organic EL display device or the like, improvement of the oblique reflection hue can be expected in addition to the improvement of the front reflection hue. Each of the liquid crystal retardation films may be tilt-aligned, or may form a cholesteric alignment state. Furthermore, when the optical laminate includes two or more phase difference films, it is preferable that at least one phase difference film is adjacent to the resin layer Y, and it is even more preferable that a phase difference film having a λ / 4 wave plate function is adjacent to the resin layer Y. In embodiments including multiple phase difference films, phase difference films other than those adjacent to the resin layer Y may be bonded to other layers, for example, by conventionally known adhesives, or they may be laminated by directly applying a phase difference film forming composition to other layers.

[0139] The polymerizable liquid crystal compound (B) for forming the phase difference film can be appropriately selected from polymerizable liquid crystal compounds conventionally known in the field of phase difference plates, depending on the desired optical properties. In the present invention, the polymerizable liquid crystal compound (B) can be classified, for example, into rod-shaped type (rod-shaped liquid crystal compound) and disc-shaped type (disc-shaped liquid crystal compound, discotic liquid crystal compound) based on its shape, and any of these liquid crystal compounds can be used. Furthermore, two or more rod-shaped liquid crystal compounds, two or more disc-shaped liquid crystal compounds, or mixtures of rod-shaped and disc-shaped liquid crystal compounds may be used.

[0140] Polymerizable liquid crystal compound (B) is a compound having at least one polymerizable group and possessing liquid crystal properties. Generally, polymerizable liquid crystal compounds (B) include polymerizable liquid crystal compounds that exhibit positive wavelength dispersibility and polymerizable liquid crystal compounds that exhibit inverse wavelength dispersibility, obtained by polymerizing the polymerizable liquid crystal compound alone in a specific orientation (cured product). In the present invention, only one type of polymerizable liquid crystal compound may be used, or both types may be mixed and used. Furthermore, for example, if the optical laminate includes a phase difference film having a λ / 4 wave plate function and a phase difference film that is a positive C plate, the polymerizable liquid crystal compounds constituting these may be the same or different.

[0141] In the present invention, the polymerizable group of the polymerizable liquid crystal compound (B) that forms the phase difference film is preferably a photopolymerizable group, and examples of polymerizable groups include those exemplified as polymerizable groups of the polymerizable liquid crystal compound (A) that can constitute a liquid crystal polarizing film. Among these, acryloyloxy groups, methacryloyloxy groups, vinyloxy groups, oxyranyl groups, and oxetanyl groups are more preferred, and acryloyloxy groups or methacryloyloxy groups are even more preferred. The liquid crystalline properties may be either thermotropic or lyotropic liquid crystals, but thermotropic liquid crystals are preferred because they allow for precise control of film thickness. Furthermore, the phase order structure in the thermotropic liquid crystal may be either nematic or smectic liquid crystals. As the polymerizable liquid crystal compound (B), one type may be used, or two or more types may be used in combination.

[0142] When the optical laminate of the present invention includes a phase difference film having a λ / 4 wave plate function, the polymerizable liquid crystal compound (B) that forms the phase difference film having a λ / 4 wave plate function preferably includes a polymerizable liquid crystal compound having a T-shaped or H-shaped mesogenic structure that further exhibits birefringence in the direction perpendicular to the molecular long axis, from the viewpoint of exhibiting inverse wavelength dispersion, and more preferably includes a T-shaped polymerizable liquid crystal compound from the viewpoint of obtaining stronger dispersion.

[0143] A polymerizable liquid crystal compound having a T-shaped liquid crystal structure is, for example, the following formula (B1): P 1 -E 1 -( B 1 -G 1 ) k -L 1 -Ar-L 2 -(G 2 -B 2 ) l -E 2 -P 2 (B1) Examples include compounds represented by (hereinafter also referred to as "polymerizable liquid crystal compounds (B1)").

[0144] In formula (B1), Ar represents a divalent aromatic group which may have substituents. Preferably, the divalent aromatic group contains at least one of nitrogen, oxygen, and sulfur atoms. If the divalent group Ar contains two or more aromatic groups, the two or more aromatic groups may be linked to each other by single bonds, divalent bonding groups such as -CO-O- and -O-. G 1 and G 2 Each of these independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atoms contained in the divalent aromatic group or divalent alicyclic hydrocarbon group may be substituted with halogen atoms, C1-C4 alkyl groups, C1-C4 fluoroalkyl groups, C1-C4 alkoxy groups, cyano groups, or nitro groups, and the carbon atoms constituting the divalent aromatic group or divalent alicyclic hydrocarbon group may be substituted with oxygen atoms, sulfur atoms, or nitrogen atoms. L 1 , L 2 、 B 1 and B 2 Each of these is independently a single bond or a divalent linking group. k and l each represent integers from 0 to 3 independently, satisfying the relationship 1 ≤ k + l. Here, if 2 ≤ k + l, then B 1 and B 2 , G 1 and G 2 These elements may be identical to each other, or they may be different. E 1 and E 2 Each of these independently represents an alkanediyl group having 1 to 17 carbon atoms, where the hydrogen atoms in the alkanediyl group may be substituted with halogen atoms, and the -CH2- groups in the alkanediyl group may be substituted with -O-, -S-, or -COO-, and if there are multiple -O-, -S-, or -COO- groups, they are not adjacent to each other. 1 and P 2 Each of these independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.

[0145] G 1 and G 2Each of these is independently preferably a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, more preferably a methyl-substituted 1,4-phenylenediyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group, and particularly preferably an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexandiyl group. Also, there are multiple G 1 and G 2 Preferably, at least one of them is a divalent alicyclic hydrocarbon group, and L 1 or L 2 G that joins 1 and G 2 It is more preferable that at least one of these is a divalent alicyclic hydrocarbon group.

[0146] L 1 and L 2 Each of these is independently, preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 Ure a2 -, -R a3 COOR a4 -, -R a5 OCOR a6 -, -R a7 OC=OOR a8 -, -N=N-, -CR c =CR d -, or -C≡C-. Here, R a1 ~R a8 Each of these independently represents a single bond or an alkylene group with 1 to 4 carbon atoms, R c and R d L represents an alkyl group or hydrogen atom with 1 to 4 carbon atoms. 1 and L 2 Each is independently, more preferably a single bond, -OR a2-1 -, -CH2-, -CH2CH2-, -COORa4-1 -, or -OCOR a6-1 - is the case here R a2-1 , R a4-1 , R a6-1 Each of these independently represents either a single bond, -CH2-, or -CH2CH2-. 1 and L 2 Each of these is independently, and more preferably, a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or -OCO-.

[0147] B 1 and B 2 Each of these is independently, preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 Ure a10 -, -R a11 COOR a12 -, -R a13 OCOR a14 -, or -R a15 OC=OOR a16 - is the case here R a9 ~R a16 Each of these independently represents a single bond or an alkylene group with 1 to 4 carbon atoms. 1 and B 2 Each is independently, more preferably a single bond, -OR a10-1 -, -CH2-, -CH2CH2-, -COOR a12-1 -, or -OCOR a14-1 - is the case here R a10-1 , R a12-1 , R a14-1 Each of these independently represents either a single bond, -CH2-, or -CH2CH2-. 1 and B 2 Each of these is independently, and more preferably, a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or -OCOCH2CH2-.

[0148] From the viewpoint of exhibiting inverse wavelength dispersion, k and l are preferably in the range of 2 ≤ k + l ≤ 6, preferably k + l = 4, and more preferably k = 2 and l = 2. A symmetric structure is preferred when k = 2 and l = 2.

[0149] E 1 and E 2 Each of these groups is independently preferably an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms.

[0150] P 1 or P 2 Examples of polymerizable groups represented by include epoxy groups, vinyl groups, vinyloxy groups, 1-chlorovinyl groups, isopropenyl groups, 4-vinylphenyl groups, acryloyloxy groups, methacryloyloxy groups, oxyranyl groups, and oxetanyl groups. Among these, acryloyloxy groups, methacryloyloxy groups, vinyloxy groups, oxyranyl groups, and oxetanyl groups are preferred, with acryloyloxy groups being more preferred.

[0151] It is preferable that Ar has at least one selected from an aromatic hydrocarbon ring which may have substituents, an aromatic heterocycle which may have substituents, and an electron-withdrawing group. Examples of the aromatic hydrocarbon ring include a benzene ring, a naphthalene ring, an anthracene ring, etc., with benzene rings and naphthalene rings being preferred. Examples of the aromatic heterocycle include a furan ring, a benzofuran ring, a pyrrole ring, an indole ring, a thiophene ring, a benzothiophene ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a triazole ring, a triazine ring, a pyrroline ring, a pyrodazole ring, an imidazole ring, a pyrazole ring, a thiazole ring, a benzothiazole ring, a thienothiazole ring, an oxazole ring, a benzoxazole ring, and a phenantholine ring, etc. Among these, it is preferable to have a thiazole ring, a benzothiazole ring, or a benzofuran ring, and it is even more preferable to have a benzothiazole group. Furthermore, if Ar contains a nitrogen atom, it is preferable that the nitrogen atom has π electrons.

[0152] In formula (B1), N is the total number of π electrons contained in the divalent aromatic group represented by Ar. πis preferably 8 or more, more preferably 10 or more, still more preferably 14 or more, and particularly preferably 16 or more. Also, it is preferably 36 or less, more preferably 32 or less, still more preferably 26 or less, and particularly preferably 24 or less.

[0153] Preferable examples of the aromatic group represented by Ar include the following groups.

[0154]

Chemical Formula

[0155] In formulas (Ar-1) to (Ar-23), the * mark represents a linking site, and Z 0 , Z 1 and Z 2 each independently represent a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms.

[0156] Q 1 , and Q 2 each independently represent -CR 2’ R 3’ -, -S-, -NH-, -NR 2’ -, -CO- or -O-, and R 2’ and R 3’ each independently represent a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

[0157] J 1 , and J 2 each independently represent a carbon atom or a nitrogen atom.

[0158] Y 1 , and Y2 Each of these independently represents an optionally substituted aromatic hydrocarbon group or an aromatic heterocyclic group.

[0159] W 1 and W 2 Each of these independently represents a hydrogen atom, a cyano group, a methyl group, or a halogen atom, and m represents an integer from 0 to 6.

[0160] Y 1 , and Y 2 Examples of aromatic hydrocarbon groups in this context include C6-C20 aromatic hydrocarbon groups such as phenyl, naphthyl, anthuryl, phenanthuryl, and biphenyl groups, with phenyl and naphthyl groups being preferred and phenyl groups being more preferred. Examples of aromatic heterocyclic groups include C4-C20 aromatic heterocyclic groups containing at least one heteroatom such as a nitrogen atom, oxygen atom, or sulfur atom, such as furyl, pyrrolyl, thienyl, pyridinyl, thiazolyl, and benzothiazolyl groups, with furyl, thienyl, pyridinyl, thiazolyl, and benzothiazolyl groups being preferred.

[0161] Y 1 , and Y 2 Each of these may independently be a substituted polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group. A polycyclic aromatic hydrocarbon group refers to a fused polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring assembly. A polycyclic aromatic heterocyclic group refers to a fused polycyclic aromatic heterocyclic group or a group derived from an aromatic ring assembly.

[0162] Z 0 , Z 1 and Z 2 Each of these is preferably independently a hydrogen atom, a halogen atom, a C1-C12 alkyl group, a cyano group, a nitro group, or a C1-C12 alkoxy group, Z 0 A hydrogen atom, an alkyl group having 1 to 12 carbon atoms, and a cyano group are more preferably Z 1 and Z 2 Hydrogen atoms, fluorine atoms, chlorine atoms, methyl groups, and cyano groups are more preferred.

[0163] Q 1 , and Q 2 -NH-, -S-, -NR 2’ -, -O- is preferred, R 2’ A hydrogen atom is preferred. Among these, -S-, -O-, and -NH- are particularly preferred.

[0164] Among formulas (Ar-1) to (Ar-23), formulas (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability. In equations (Ar-17) to (Ar-23), Y 1 This is the nitrogen atom and Z that it bonds to. 0 It may also form an aromatic heterocyclic group. Examples of aromatic heterocyclic groups that Ar may have include those mentioned above, such as a pyrrole ring, imidazole ring, pyrroline ring, pyridine ring, pyrazine ring, pyrimidine ring, indole ring, quinoline ring, isoquinoline ring, purine ring, pyrrolidine ring, etc. This aromatic heterocyclic group may have substituents. Also, Y 1 This is the nitrogen atom and Z that it bonds to. 0 In addition, the aforementioned substituted polycyclic aromatic hydrocarbon groups or polycyclic aromatic heterocyclic groups may also be used. Examples include benzofuran rings, benzothiazole rings, and benzoxazole rings.

[0165] Polymerizable liquid crystal compound (B1) can be produced, for example, by the method described in Japanese Patent Application Publication No. 2010-31223.

[0166] In one embodiment of the present invention, the polymerizable liquid crystal compound (B) is preferably a compound having a maximum absorption wavelength of 300 to 400 nm. Having the maximum absorption wavelength within this range is advantageous in terms of the stability of the phase difference film forming composition, and improves the orientation and uniformity of the film thickness of the resulting liquid crystal phase difference film. The maximum absorption wavelength of the polymerizable liquid crystal compound (B) can be measured in a solvent using an ultraviolet-visible spectrophotometer. The solvent is capable of dissolving the polymerizable liquid crystal compound (B), and examples include chloroform.

[0167] In the present invention, as the polymerizable liquid crystal compound (B) for forming the liquid crystal phase difference film, in addition to polymerizable liquid crystal compound (B1), or in place thereof, polymerizable liquid crystal compounds such as those described in Japanese Patent Publication No. 2010-31223, Japanese Patent Publication No. 2010-270108, Japanese Patent Publication No. 2011-6360 and Japanese Patent Publication No. 2011-207765, polymerizable liquid crystal compounds exhibiting so-called positive wavelength dispersion, or the polymerizable liquid crystal compound (A1) exemplified above may be used. All of these polymerizable liquid crystal compounds can be used in either a horizontal or vertical orientation.

[0168] The content of polymerizable liquid crystal compound (B) in the phase difference film forming composition can be appropriately determined depending on the desired optical properties of the optical laminate, the type of polymerizable liquid crystal compound (B) used, etc. The content of polymerizable liquid crystal compound (B) in the phase difference film forming composition is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and even more preferably 90 to 95 parts by mass, per 100 parts by mass of solid content of the phase difference film forming composition. If the content of polymerizable liquid crystal compound (B) is within the above range, it is advantageous from the viewpoint of the orientation of the resulting liquid crystal phase difference film.

[0169] In one embodiment of the present invention, when a composition for forming a phase difference film having a λ / 4 waveplate function contains polymerizable liquid crystal compounds other than polymerizable liquid crystal compound (B1), from the viewpoint of optical properties, the ratio of polymerizable liquid crystal compound (B1) to the total mass of all polymerizable liquid crystal compounds (B) in the phase difference film forming composition is preferably 51% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. The polymerizable liquid crystal compound (B) may all be polymerizable liquid crystal compound (B1), but from the viewpoint of liquid crystal phase transition temperature, the upper limit may be, for example, 98% by mass or 95% by mass.

[0170] The composition for forming a phase difference film may contain additives such as polymerization initiators, solvents, and leveling agents in addition to the polymerizable liquid crystal compound. As the polymerization initiator, a photopolymerization initiator that generates active radicals or acids upon the action of light is preferred, and a photopolymerization initiator that generates radicals upon the action of light is more preferred, as it allows the polymerization reaction to be initiated under lower temperature conditions. The polymerization initiator may be used alone or in combination of two or more types.

[0171] As the photopolymerization initiator, known photopolymerization initiators can be used. For example, as a photopolymerization initiator that generates active radicals, those similar to those previously exemplified as usable in the resin composition (Y) can be used, and should be appropriately selected in relation to the polymerizable liquid crystal compound (B) that forms the phase difference film.

[0172] The polymerization initiator content is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 15 parts by mass, even more preferably 0.5 to 10 parts by mass, and particularly preferably 0.5 to 8 parts by mass, per 100 parts by mass of polymerizable liquid crystal compound (B). When the polymerization initiator content is within the above range, the polymerization reaction can be carried out without significantly disrupting the orientation of the polymerizable liquid crystal compound.

[0173] Examples of solvents, leveling agents, and additives include those similar to those previously exemplified as usable in the polarizing film-forming composition, and each can be used in an amount approximately the same as that used in the polarizing film-forming composition.

[0174] The phase difference film forming composition can be prepared by conventionally known liquid crystal composition preparation methods, and is typically prepared by mixing and stirring a polymerizable liquid crystal compound (B) and, if necessary, a polymerization initiator, solvent, and the above-mentioned additives.

[0175] In the present invention, the liquid crystal retardation film can be formed on an alignment film. Examples of the alignment film include those similar to those previously exemplified as usable when producing a liquid crystal polarizing film, and may be appropriately selected according to the desired alignment regulating force and the like. In one embodiment of the present invention, a photo-alignment film is preferred from the viewpoints of easy enhancement of alignment accuracy, adhesion to the liquid crystal retardation film, and the like.

[0176] The thickness of the alignment film is usually 10 to 5000 nm, preferably 10 to 1000 nm, more preferably 10 to 500 nm, still more preferably 10 to 300 nm, and particularly preferably 30 to 300 nm. When the thickness of the alignment film is within the above range, good adhesion is exhibited at the interface with the liquid crystal retardation film formed on the alignment film, the alignment regulating force can be exerted, and a polarizing film can be formed with high alignment order.

[0177] The liquid crystal retardation film can be produced by, for example, a method comprising forming a coating film of a composition for forming a retardation film, removing the solvent from the coating film, raising the temperature to a temperature equal to or higher than the temperature at which the polymerizable liquid crystal compound (B) undergoes phase transition to a liquid phase, then lowering the temperature to cause the polymerizable liquid crystal compound (B) to undergo phase transition to a liquid crystal phase, and polymerizing the polymerizable liquid crystal compound (B) while maintaining the liquid crystal phase .

[0178] Examples of methods that can be employed for the application method of the composition for forming a retardation film, the curing of the polymerizable liquid crystal compound (B) by light irradiation, and the like include the same methods as those previously exemplified in the methods for forming the resin layer Y and the liquid crystal polarizing film.

[0179] The thickness of the liquid crystal retardation film can be appropriately selected according to the display device to be applied. In one embodiment of the present invention, the thickness of the liquid crystal retardation film is preferably 0.5 μm to 5 μm, more preferably 1 μm to 3 μm.

[0180] The laminate of the present invention, which includes a polarizing film, a resin layer X, and a resin layer Y adjacent to each other in this order, can be manufactured, for example, by applying a resin composition (X) to one side of the polarizing film to form a resin layer X, and then applying a resin composition (Y) on the resin layer X to form a resin layer Y. In one embodiment of the present invention, the optical laminate of the present invention preferably includes a polarizing film, a resin layer X, a resin layer Y, and a phase difference film adjacent to the resin layer Y in this order. Such an optical laminate can be manufactured, for example, by separately manufacturing an optical laminate including a phase difference film from an optical laminate comprising a polarizing film, a resin layer X, and a resin layer Y, and then bonding the optical laminate including the polarizing film and the optical laminate including the phase difference film via a resin layer Y. In this case, it is preferable to laminate the liquid crystal phase difference film so that the slow axis (optical axis) and the absorption axis of the liquid crystal polarizing film are substantially 45° apart. By laminating the liquid crystal phase difference film so that the slow axis (optical axis) and the absorption axis of the polarizing film are substantially 45° apart, the function of a circular polarizer can be obtained. In this specification, "substantially 45°" means 45° ± 5°.

[0181] The optical laminate of the present invention may include, in addition to the polarizing film, resin layer X, resin layer Y, and phase difference film adjacent to the resin layer Y, other layers, as long as they do not affect the effects of the present invention. Examples of other layers include phase difference films other than the phase difference film adjacent to the resin layer Y, protective layers for the polarizing film, adhesive layers, etc.

[0182] The optical laminate of the present invention exhibits excellent durability in high-temperature and high-humidity environments, is less prone to degradation of polarization performance, and allows for the lamination of a polarizing film and a phase difference film with high adhesion. Therefore, it can be suitably used, for example, as a circular polarizer or as a component of an organic EL display device. A display device is a device having a display element, and includes a light-emitting element or a light-emitting device as a light source. Examples of display devices include liquid crystal displays, organic electroluminescent (EL) displays, inorganic electroluminescent (EL) displays, touch panel displays, electron emission displays (e.g., electric field emission displays (FEDs), surface field emission displays (SEDs)), electronic paper (display devices using electronic ink or electrophoretic elements), plasma displays, projection displays (e.g., grating light bulb (GLV) displays, displays having digital micromirror devices (DMDs)), and piezoelectric ceramic displays. Liquid crystal displays include transmissive liquid crystal displays, semi-transmissive liquid crystal displays, reflective liquid crystal displays, direct-view liquid crystal displays, and projection liquid crystal displays. These displays may be displays that show two-dimensional images or stereoscopic displays that show three-dimensional images. In particular, the optical laminate of the present invention can be suitably used in organic electroluminescent (EL) displays and inorganic electroluminescent (EL) displays, and can also be suitably used in liquid crystal displays and touch panel displays. These displays can exhibit good image display characteristics because the optical laminate of the present invention has excellent durability and can achieve high visibility. [Examples]

[0183] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" refer to "parts by mass" and "mass%" unless otherwise specified.

[0184] 1. Preparation of resin composition (Y) (1) Resin composition (Y-1)~(Y-9) The curable compounds were stirred and mixed for 30 minutes according to the compositions listed in Table 1. Then, the photopolymerization initiator was added and stirred and mixed for 24 hours to prepare resin compositions (Y-1) to (Y-9). In Table 1, the amount of the polymerization initiator represents the parts of solids.

[0185] [Table 1]

[0186] The abbreviations for each component used in Table 1 are as follows: • A-9550: Dipentaerythritol polyacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product name "A-9550", viscosity: 6500 mPa·s / 25℃, molecular weight: 578.20 g / mol, number of functional groups ((meth)acrylate groups): 6) • 4-HBA: 4-Hydroxybutyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., product name "4-HBA", viscosity: 5.5 mPa·s, molecular weight: 144.2 g / mol, number of functional groups ((meth)acrylate group): 1) • UV-7605B: Urethane acrylate oligomer (manufactured by Mitsubishi Chemical Corporation, product name "UV-7605B", viscosity: 800-1400 mPa·s / 60℃, molecular weight: 1100 g / mol, number of functional groups ((meth)acrylate groups): 6) A-LEN-10: Ethoxylated o-phenylphenol acrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., product name "A-LEN-10", viscosity: 130 mPa·s / 25℃, molecular weight: 268.31 g / mol, refractive index: 1.58, number of functional groups ((meth)acrylate group): 1) BA: Butyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd., product name "Butyl Acrylate (stabilized with MEHQ)", molecular weight: 128.17 g / mol) • Omnirad819: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (manufactured by IGM Resins BV, trade name "Omnirad819", molecular weight: 418.5 g / mol, molar extinction coefficient at light source wavelength of 400 nm: 1125 L·mol) -1 ·cm -1 )

[0187] (2) Resin composition (Y-10) After mixing the following components, excluding the polymerization initiator, and stirring for 30 minutes, the polymerization initiator was added and stirred for 24 hours to obtain a cationic curable resin composition (Y-10). (curable compound) · 3',4'-Epoxycyclohexylmethyl 3,4-Epoxycyclohexanecarboxylate (Trade name: CEL2021P, manufactured by Daicel Corporation): 32.5 parts • 1,2-epoxy-4-(2-oxyranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (trade name: EHPE3150, manufactured by Daicel Corporation): 7.5 parts • 3-Ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane (product name: OXT-221, manufactured by Toagosei Co., Ltd.): 60 parts (Sensitizer) • 1,4-Diethoxynaphthalene (leveling agent): 2.0 parts (Leveling agent) • Silicone-based leveling agent (product name: SH710, manufactured by Toray Dow Corning Co., Ltd.): 0.25 parts (Polymerization initiator) • Cationic polymerization initiator (product name: CPI-100P, 50% by mass solution, manufactured by Sunapro Co., Ltd.): 2.25 parts

[0188] 2. Fabrication of optical stacks <Optical laminate of Example 1> (1) Fabrication of a laminated film with a polarizing film (i) Preparation of composition (1) for forming photoalignment film Copolymer (1) having the following structure was prepared using the procedure described below. In the structure below, l, m, and n are integers between 0 and 100, and l + m + n = 100. [ka]

[0189] 4-((6-(methacryloyloxy)hexyl)oxy)benzoic acid was dissolved in toluene along with an amine catalyst. Chlorodimethyl ether was added dropwise to this solution, and the reaction was allowed to proceed by heating and maintaining the temperature at 40°C. After the reaction mixture was cooled, water was added. The organic layer was separated from the resulting mixture, and a 50% aqueous acetic acid solution was added to the separated organic layer and stirred to obtain a mixture. The organic layer was separated from the resulting mixture, and the separated organic layer was concentrated to obtain methoxymethyl 4-((6-(methacryloyloxy)hexyl)oxy)benzoate. 8.8 g (25.2 mmol) of methoxymethyl 4-((6-(methacryloyloxy)hexyl)oxy)benzoate, 1.0 g (3.6 mmol) of 6-(4-hydroxyphenoxy)hexyl methacrylate, 3.2 g (7.2 mmol) of 4-((6-methacryloyloxy)hexyl)oxy)phenyl(E)-3-(4-methoxyphenyl)acrylate, and 0.2 g of 2,2'-azobis(2,4-dimethylvaleronitrile) were dissolved in tetrahydrofuran. After passing nitrogen through this solution for 1 hour, the reaction was allowed to proceed by heating and maintaining the temperature at 60°C, and the reaction mixture was cooled to room temperature. To this reaction mixture, 1.1 g (3.6 mmol) of 4-((6-(methacryloyloxy)hexyl)oxy)benzoic acid and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride were added to obtain a mixture. The reaction was initiated by heating the mixture to 40°C, after which the reaction mixture was cooled. Methanesulfonic acid was added to this reaction mixture at room temperature, and after heating to 70°C, the reaction mixture was cooled to near room temperature. The cooled reaction mixture was added dropwise to n-hexane to form a precipitate, which was collected and dried under reduced pressure to obtain the polymer. The weight-average molecular weight of copolymer (1) was measured by GPC and found to be 24,000.

[0190] Next, 2 parts of the obtained copolymer (1) and 98 parts of propylene glycol methyl ether acetate were mixed to obtain a mixture. The obtained mixture was stirred at 80°C for 1 hour to obtain the photo-alignment film forming composition (1).

[0191] (ii) Preparation of a composition for forming a polarizing film A polarizing film-forming composition was obtained by mixing the components listed below and stirring at 80°C for 1 hour. The polymerizable liquid crystal compound (a1), polymerizable liquid crystal compound (a2), and dichroic dyes (DP1) to (DP3) each have the structures shown below. ·Polymerizable liquid crystal compound (a1): 75 parts ·Polymerizable liquid crystal compound (a2): 25 parts ·Dichroic dye (DP1): 2.5 parts • Dichroic dye (DP2): 2.5 parts • Dichroic dye (DP3): 2.5 parts • Polymerization initiator [2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one (Irgacure® 369; manufactured by BASF Japan): 6 parts • Leveling agent [polyacrylate compound (BYK-361N; manufactured by BYK-Chemie)]: 1.2 parts • Solvent [o-xylene]: 250 parts

[0192] Polymerizable liquid crystal compound (a1) [ka] Polymerizable liquid crystal compound (a2) [ka] Dichroic dye (DP1) [ka] Dichroic pigment (DP2) [ka] Dichroic pigment (DP3) [ka]

[0193] (iii) Fabrication of a polarizing film-coated laminated film The surface of the hard coat layer of a release film with a hard coat layer was subjected to corona treatment. A photoalignment film-forming composition (1) was applied to the corona-treated surface using a coating apparatus, dried at 80°C for 1 minute, and then treated with a polarizing UV irradiation device (SPOTCURESP-9 with polarizer unit; manufactured by Ushio Inc.) at 50 mJ / cm². 2 Polarized UV exposure with integrated light intensity (under an air atmosphere, integrated light intensity at a wavelength of 313 nm: 50 mJ / cm²) 2 A photo-aligned film (1) was formed by performing the following procedure. Furthermore, the thickness of the obtained photo-aligned film (1) was measured using an ellipsometer M-220 (manufactured by JASCO Corporation) and was found to be 100 nm.

[0194] The obtained photo-alignment film (1) was coated with a polarizing film-forming composition using a coating apparatus, and then heated and dried in a drying oven set to 120°C for 1 minute to obtain a dried film. Next, ultraviolet light was irradiated onto the dried film side of the polarizing film-forming composition using a UV irradiation device (UniCure VB-15201BY-A, manufactured by Ushio Inc.) (under a nitrogen atmosphere, integrated light intensity at a wavelength of 365 nm: 500 mJ / cm²). 2 By doing so, a liquid crystal polarizing film in which polymerizable liquid crystal compounds and dichroic dyes are oriented was formed. This resulted in a laminated film with a polarizing film consisting of a release film / hard coat layer / photo-alignment film (1) / liquid crystal polarizing film. The thickness of the polarizing film was measured using an ellipsometer M-220 (manufactured by JASCO Corporation) and found to be 2.0 μm. Furthermore, X-ray diffraction measurements were performed on the polarizing film using an X-ray diffractometer X'PertPROMPD (manufactured by SPECTRIS Corporation). The result showed a sharp diffraction peak (Bragg peak) with a peak half-width (FWHM) of approximately 0.17° at around 2θ = 20.2°. The order period (d) determined from the peak position was approximately 4.4 Å, confirming the formation of a structure reflecting a higher-order smectic phase.

[0195] (2) Fabrication of laminated film with resin layer X1 A resin composition (X1) (aqueous solution with a solid content of 3.7%) containing an acetoacetyl group-modified polyvinyl alcohol resin (Mitsubishi Chemical Corporation, "Gosenor Z-200") and water was coated onto the liquid crystal polarizing film of the above-mentioned laminated film with a polarizing film, so that the thickness after drying was 0.5 μm, and the resin layer X1 was formed by drying at a temperature of 80°C for 2 minutes. This resulted in a laminated film with a resin layer X1 consisting of a release film / hard coat layer / photoalignment film (1) / liquid crystal polarizing film / resin layer X1.

[0196] (3) Fabrication of laminated film with phase difference film (1) (i) Preparation of composition (2) for forming photoalignment film A photo-oriented material with the following structure (weight-average molecular weight: 50,000, m:n=50:50) was manufactured according to the method described in Japanese Patent Publication No. 2021-196514. Two parts by mass of the photo-oriented material and 98 parts by mass of cyclopentanone (solvent) were mixed, and the resulting mixture was stirred at 80°C for 1 hour to prepare a photo-oriented film-forming composition (2). [ka]

[0197] (ii) Preparation of the composition (1) for forming a phase difference film Polymerizable liquid crystal compounds (b1) and (b2), having the structures shown below, were prepared, respectively. ·Polymerizable liquid crystal compound (b1): [ka] ·Polymerizable liquid crystal compound (b2): [ka]

[0198] A solution was obtained by dissolving 1 mg of polymerizable liquid crystal compound (b1) in 10 mL of chloroform. The obtained solution was placed in a measuring cell with a path length of 1 cm to prepare the sample for measurement, and the measurement sample was set in a UV-Vis spectrophotometer (Shimadzu Corporation "UV-2450") to measure the absorption spectrum. When the wavelength at which the absorption maximum was obtained was read from the obtained absorption spectrum, the maximum absorption wavelength λmax in the wavelength range of 300 to 400 nm was found to be 356 nm.

[0199] Polymerizable liquid crystal compound (b1) and polymerizable liquid crystal compound (b2) were mixed in a mass ratio of 90:10 to obtain a mixture. To 100 parts by mass of the obtained mixture, 0.1 parts by mass of the leveling agent "BYK-361N" (manufactured by BMChemie) and 3 parts by mass of "Irgacure OXE-03" (manufactured by BASF Japan Ltd.) as a photopolymerization initiator were added. Furthermore, N-methyl-2-pyrrolidone (NMP) was added to achieve a solid content concentration of 13% by mass. By stirring this mixture at a temperature of 80°C for 1 hour, a phase difference film forming composition (1) was obtained.

[0200] (iii) Fabrication of laminated films with phase difference coatings The release surface of the release film was subjected to corona treatment, and the photo-alignment film-forming composition (2) was applied to the surface of the corona-treated release film using an adhesive coating device. The resulting coating film was dried at 120°C for 2 minutes, and then cooled to room temperature to form a dried film. Subsequently, the photo-alignment film (2) was obtained by irradiating it with polarized ultraviolet light at 100 mJ (313 nm reference) using a UV irradiation device (SPOTCURESP-9; manufactured by Ushio Inc.). Furthermore, when the thickness of the photo-alignment film (2) was measured using an ellipsometer M-220 manufactured by JASCO Corporation, the thickness of the photo-alignment film (2) was found to be 100 nm.

[0201] The above-mentioned phase difference film forming composition (1) was applied to the obtained photo-alignment film (2) using a coating apparatus to form a coated film. This coated film was heated and dried at 120°C for 2 minutes, then cooled to room temperature to obtain a dried film. Next, an exposure dose of 500 mJ / cm² was applied using a high-pressure mercury lamp (UniCure VB-15201BY-A manufactured by Ushio Inc.) under a nitrogen atmosphere. 2 By irradiating the dried film with ultraviolet light (based on 365 nm), a liquid crystal phase difference film (1) was formed in which the polymerizable liquid crystal compound was cured in a state in which it was oriented horizontally with respect to the substrate surface, and a laminated film with the phase difference film (1) was obtained. The structure of the obtained laminated film with the phase difference film (1) was release film / photoalignment film (2) / liquid crystal phase difference film (1) (horizontally oriented liquid crystal cured film having λ / 4 wave plate function). Furthermore, when the thickness of the phase difference film (1) was measured using a laser microscope LEXTOLS4100 manufactured by Olympus Corporation, the thickness of the phase difference film (1) was found to be 2.0 μm.

[0202] (4) Fabrication of laminated film with phase difference film (2) (i) Preparation of compositions for forming vertically aligned films As a composition for forming vertically aligned films, a mixture was used which consisted of 2-phenoxyethyl acrylate, tetrahydrofurfuryl acrylate, dipentaerythritol triacrylate, and bis(2-vinyloxyethyl) ether in a ratio of 1:1:4:5, with LUCIRINTPO added as a polymerization initiator at a ratio of 4% by mass relative to the composition for forming vertically aligned films.

[0203] (ii) Preparation of the composition (2) for forming a phase difference film A mixed solvent was prepared by mixing methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), and cyclohexanone (CHN) in a mass ratio (MEK:MIBK:CHN) of 35:30:35. A photopolymerizable nematic liquid crystal compound (Merck, RMM28B) was mixed into 100 parts by mass of the mixed solvent to prepare a phase difference film forming composition (2) with a solid content of 1 to 1.5 parts by mass.

[0204] (iii) Preparation of laminated film with phase difference film (2) A vertical alignment film-forming composition is applied to the release-treated surface of a release-treated polyethylene terephthalate film (38 μm thick), and 200 mJ / cm² is applied. 2 A vertically aligned film was fabricated by irradiating it with ultraviolet light. The thickness of the obtained vertically aligned film was 30 nm.

[0205] A phase difference film-forming composition (2) was applied to a vertically aligned film by die coating. The coating solution was dried at a drying temperature of 75°C for 120 seconds. Subsequently, the coating was irradiated with ultraviolet (UV) light to polymerize the polymerizable liquid crystal compound, obtaining a laminated film with a phase difference film (2). The resulting laminated film with a phase difference film (2) consisted of a liquid crystal phase difference film (2), a vertically aligned film, and a polyethylene terephthalate film. The thickness of the phase difference film (2) was measured using an Olympus Corporation LEXTOLS4100 laser microscope, and the thickness of the phase difference film (2) was found to be 1.0 μm.

[0206] (5) Fabrication of the laminate (1) Corona treatment was applied to the surface of the phase difference film of the laminated film with phase difference film (1) and the laminated film with phase difference film (2), and the phase difference film (1) and phase difference film (2) were bonded together using a cationic adhesive composition so that they formed a bonding surface. Next, the cationic adhesive composition was cured by irradiation with ultraviolet light to produce laminate (1). The resulting laminate (1) consisted of a release film / photo-alignment film (2) / liquid crystal phase difference film (1) / cationic adhesive layer / liquid crystal phase difference film (2) / vertical alignment film / polyethylene terephthalate film (release film). The cationic adhesive composition was prepared according to the following procedure. The curing component, leveling agent, and sensitizing agent listed below were stirred and mixed for 30 minutes. Then, a polymerization initiator was added and stirred and mixed for a further 24 hours to obtain a cationic adhesive composition. Note that the polymerization initiator represents the parts of solids. (curable component) • 3',4'-Epoxycyclohexylmethyl 3,4-Epoxycyclohexanecarboxylate (Trade name: CEL2021P, manufactured by Daicel Corporation): 70 units • Neopentyl glycol diglycidyl ether (product name: EX-211, manufactured by Nagase ChemteX Corporation): 20 units • 2-Ethylhexylglycidyl ether (manufactured by Tokyo Chemical Industry Co., Ltd.): 10 parts (Sensitizer) • 1,4-Diethoxynaphthalene: 2.0 parts (Leveling agent) • Silicone-based leveling agent (product name: SH710, manufactured by Toray Dow Corning Co., Ltd.): 0.25 parts (Polymerization initiator) • Cationic polymerization initiator (product name: CPI-100P, 50% by mass solution, manufactured by Sunapro Co., Ltd.): 2.25 parts

[0207] (6) Fabrication of the laminate (2-1) The release film on the photo-alignment film (2) side of the laminate (1) was peeled off, and the surface of the photo-alignment film (2) was subjected to corona treatment. Then, the resin composition (Y-1) was applied to the corona-treated surface using a coating apparatus to form a coated layer. In addition, the surface of the resin layer X1 of the laminated film with resin layer X1 was subjected to corona treatment, and the resin layer X1 side was laminated against the surface of the laminate (1) coated with resin composition (Y-1). An ultraviolet irradiation device with a belt conveyor (the lamp is a mercury lamp manufactured by I-Graphics Co., Ltd.) was used to apply an integrated light intensity of 450 mJ / cm² from the liquid crystal phase difference film (2) side of the obtained laminate. 2 The resin composition (Y-1) was cured by irradiating it with UV light (UV-V (395-445 nm; the same applies hereafter)) to obtain a laminate (2-1). The composition of the obtained laminate (2-1) was: release film / hard coat layer / photo-alignment film (1) / liquid crystal polarizing film / resin layer X1 / resin layer Y-1 (cured layer of adhesive composition (Y-1)) / photo-alignment film (2) / liquid crystal phase difference film (1) / cationic adhesive layer / liquid crystal phase difference film (2) / vertical alignment film / release film. The thickness of the cured layer of resin composition (Y-1) was 2 μm.

[0208] (7) Fabrication of laminate (3-1) (circular polarizer) The release film on the liquid crystal polarizing film side of the laminate (2-1) was peeled off, and the hard coat layer surface was subjected to corona treatment. The adhesive layer (1) side of a release film with an adhesive layer, consisting of a 5 μm thick acrylic adhesive layer (1) and a release film, was laminated onto the corona-treated surface. Furthermore, the release film adjacent to the acrylic adhesive layer (1) was peeled off, and the corona-treated side of a 25 μm thick norbornene-based resin film (Zeonor Film ZF-14 manufactured by Nippon Zeon Co., Ltd.), which had been corona-treated on one side, was laminated to produce laminate (3-1). The resulting laminate (3-1) consisted of a norbornene-based resin film, an acrylic adhesive layer (1), a hard coat layer, a photo-alignment film (1), a liquid crystal polarizing film, a resin layer X1, a resin layer Y-1 (a cured layer of resin composition (Y-1)), a photo-alignment film (2), a liquid crystal phase difference film (1), a cationic adhesive layer, a liquid crystal phase difference film (2), a vertical alignment film, and a release film.

[0209] (8) Fabrication of laminate (4-1) (circular polarizing plate with adhesive layer) The release film on the liquid crystal phase difference film (2) side of the laminate (3-1) was peeled off, and its surface was subjected to corona treatment. The adhesive layer (2) side of a release film with an adhesive layer, consisting of a 20 μm thick acrylic adhesive layer (2) and a release film, was laminated onto the corona-treated surface to produce a laminate (4-1). The structure of the laminate (4-1) obtained here was norbornene-based resin film / acrylic adhesive layer (1) / hard coat layer / photo-alignment film (1) / liquid crystal polarizing film / resin layer X1 / resin layer Y-1 (cured layer of resin composition (Y-1)) / photo-alignment film (2) / liquid crystal phase difference film (1) / cationic adhesive layer / liquid crystal phase difference film (2) / vertical alignment film / acrylic adhesive layer (2) / release film.

[0210] (9) Fabrication of the laminate (5-1) A 25 μm thick norbornene-based resin film (Zeonor Film ZF-14, manufactured by Nippon Zeon Co., Ltd.) was subjected to corona treatment on its surface. The release film on the liquid crystal phase difference film (1) side of the laminate (1) was peeled off, and its surface was subjected to corona treatment. A resin composition (Y-1) was then applied to the corona-treated surface using a coating apparatus to form a coated layer. The corona-treated norbornene-based resin film was then laminated onto the resulting coated layer. An ultraviolet irradiation device with a belt conveyor (the lamp was a mercury lamp manufactured by I-Graphics Co., Ltd.) was used to apply an integrated light intensity of 450 mJ / cm² from the liquid crystal phase difference film (2) side of the resulting laminate. 2 The resin composition (Y-1) was cured by irradiating it with UV light (UV-V) to obtain a laminate (5-1). The composition of the obtained laminate (5-1) was norbornene-based resin film / resin layer Y-1 (cured layer of resin composition (Y-1)) / photoalignment film (2) / liquid crystal phase difference film (1) / cationic adhesive layer / liquid crystal phase difference film (2) / vertical alignment film / release film.

[0211] (10) Fabrication of the laminate (6-1) The release film of the laminate (5-1) was peeled off, and its surface was subjected to corona treatment. A release film with an adhesive layer, consisting of a 20 μm thick acrylic adhesive layer (1) and a release film, was laminated to the corona-treated surface with the adhesive layer (1) side facing outwards to obtain a laminate (6-1). The composition of the obtained laminate (6-1) was norbornene-based resin film / resin layer Y-1 (cured layer of resin composition (Y-1)) / photo-alignment film (2) / liquid crystal phase difference film (1) / cationic adhesive layer / liquid crystal phase difference film (2) / vertical alignment film / acrylic adhesive layer (1) / release film.

[0212] <Optical laminate of Example 2> Laminates (2-2), (3-2), (4-2), (5-2), and (6-2) were manufactured in the same manner as in Example 1, except that resin composition (Y-1) was changed to resin composition (Y-2).

[0213] <Optical laminate of Example 3> Laminates (2-3), (3-3), (4-3), (5-3), and (6-3) were manufactured in the same manner as in Example 1, except that resin composition (Y-1) was changed to resin composition (Y-3).

[0214] <Optical laminate of Example 4> Laminates (2-4), (3-4), (4-4), (5-4), and (6-4) were manufactured in the same manner as in Example 1, except that resin composition (Y-1) was changed to resin composition (Y-4).

[0215] <Optical laminate of Example 5> Laminates (2-5), (3-5), (4-5), (5-5), and (6-5) were manufactured in the same manner as in Example 1, except that resin composition (Y-1) was changed to resin composition (Y-5).

[0216] <Optical laminate of Example 6> Laminates (2-6), (3-6), (4-6), (5-6), and (6-6) were manufactured in the same manner as in Example 1, except that resin composition (Y-1) was changed to resin composition (Y-6).

[0217] <Optical laminate of Comparative Example 1> Laminates (2-7), (3-7), (4-7), (5-7), and (6-7) were manufactured in the same manner as in Example 1, except that resin composition (Y-1) was changed to resin composition (Y-7).

[0218] <Optical laminate of Comparative Example 2> Laminates (2-8), (3-8), (4-8), (5-8), and (6-8) were manufactured in the same manner as in Example 1, except that resin composition (Y-1) was changed to resin composition (Y-8).

[0219] <Optical laminate of Comparative Example 3> Laminates (2-9), (3-9), (4-9), (5-9), and (6-9) were manufactured in the same manner as in Example 1, except that resin composition (Y-1) was changed to resin composition (Y-9) and laminated film with resin layer X1 was changed to laminated film with resin layer X2. The laminated film with resin layer X2 was prepared as follows. A resin composition (X2) containing 3 parts by mass of a photopolymerization initiator (Omnirad819) and 100 parts by mass of butyl acrylate was applied to the liquid crystal polarizing film of the polarizing film laminated film prepared in Example 1 using an adhesive coating apparatus, and the film was coated with an integrated light intensity of 400 mJ / cm² under a nitrogen atmosphere. 2 A cured butyl acrylate layer (resin layer X2) was formed by irradiating with UV-B light to a thickness of 0.5 μm after curing. The resulting laminated film with resin layer X2 consisted of a release film, a hard coat layer, a photoalignment film (1), a liquid crystal polarizing film, and a resin layer X2.

[0220] <Optical laminate of Comparative Example 4> Laminates (2-10), (3-10), (4-10), (5-10), and (6-10) were manufactured in the same manner as in Example 1, except that resin composition (Y-1) was changed to resin composition (Y-10).

[0221] <Optical laminate of Example 7> Laminates (2-11), (3-11), (4-11), (5-11), and (6-11) were manufactured in the same manner as in Example 1, except that resin composition (Y-1) was changed to resin composition (Y-4) and laminated film with resin layer X1 was changed to laminated film with resin layer X3. The laminated film with resin layer X3 was manufactured in the same manner as the laminated film with resin layer X1, except that resin composition (X1) was replaced with resin composition (X3) (a 3.7% solids aqueous solution) containing anionic modified polyvinyl alcohol resin (manufactured by Nippon Vivaceae Co., Ltd., AP-17) and water.

[0222] <Optical laminate of Example 8> Laminates (2-12), (3-12), (4-12), (5-12), and (6-12) were manufactured in the same manner as in Example 1, except that resin composition (Y-1) was changed to resin composition (Y-4), and laminated film with resin layer X1 was changed to laminated film with resin layer X4. The laminated film with resin layer X4 was manufactured in the same manner as the laminated film with resin layer X1, except that resin composition (X1) was replaced with resin composition (X4) containing acetoacetyl group-modified polyvinyl alcohol resin (manufactured by Mitsubishi Chemical Corporation, "Gosenor Z-200"), anionic-modified polyvinyl alcohol resin (manufactured by Nippon Vinegar & Polyvinyl Alcohol Co., Ltd., AP-17), and water (3.7% solid content aqueous solution, Z-200:AP-17 (mass ratio) = 1:1).

[0223] <Optical laminate of Example 9> Laminates (2-13), (3-13), (4-13), (5-13), and (6-13) were manufactured in the same manner as in Example 1, except that resin composition (Y-1) was changed to resin composition (Y-4), and laminated film with resin layer X1 was changed to laminated film with resin layer X1'. The laminated film with resin layer X1' was manufactured in the same manner as the laminated film with resin layer X1, except that the solid content of resin composition (X1) was 1.5% (aqueous solution) and it was coated so that the thickness after drying was 0.2 μm.

[0224] 3. Evaluation of optical laminates (1) Measurement of the water contact angle of resin layers X1 and X2 The laminated film with resin layer X1 was secured to a glass plate with the side opposite to resin layer X1 in contact with the glass plate, and its edges were fixed with tape. The water contact angle with respect to the surface of resin layer X1 was measured using a contact meter (manufactured by Kyowa Interface Science Co., Ltd.) according to the static method described in R3257:1999. The water contact angle of resin layer X1 was 79°. Similarly, the water contact angles of resin layers X2, X3, and X4 of the laminated film with resin layer X2, resin layer X3, and resin layer X4 were measured, respectively. The water contact angle of resin layer X2 was 116°, resin layer X3 was 77°, and resin layer X4 was 75°. In addition, the water contact angle of resin layer X1' of the laminated film with resin layer X1' was 79°.

[0225] (2) Viscosity measurement The viscosity (at 25°C) of resin compositions (Y-1) to (Y-10) was measured using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd.) in accordance with JIS K7117-2. The results are shown in Table 2.

[0226] (3) Evaluation of coating properties The release film on the liquid crystal phase difference film (1) side of the laminate (1) is peeled off, and the photoalignment film (2) is subjected to one treatment using a corona treatment device (AGF-B10; manufactured by Kasuga Electric Co., Ltd.) at an output of 0.8 kW and a processing speed of 10 m / min (6.9 kJ / m³). 2 Next, the corona-treated surface was coated with resin composition (Y-1) and left to stand for 10 minutes at a temperature of 23°C and a humidity of 55%. After that, the coating properties were evaluated according to the following criteria by visually checking whether the resin composition (Y-1) had been coated without repelling or uneven film thickness. The coating properties were evaluated in the same manner by replacing resin composition (Y-1) with resin compositions (Y-2) to (Y-10). The results are shown in Table 2. <Evaluation Criteria> A: The coating is uniform, and the coating is applied without any repellency or unevenness in film thickness. B: Coating is possible, but the desired film thickness cannot be achieved, or some repulsion is observed.

[0227] (4) Measurement of thickness Unless otherwise specified, the thickness of each layer was measured using the Nikon MH-15M digital micrometer.

[0228] (5) In-plane average refractive index (n2) of resin layers Y-1 to Y-10 On one side of a stretched norbornene-based resin film (Zeonor Film, manufactured by Nippon Zeon Co., Ltd.), resin compositions (Y-1) to (Y-10) were coated using an adhesive coating device (manufactured by Daiichi Rika Co., Ltd.) to a thickness of approximately 30 μm after UV irradiation. Another stretched norbornene-based resin film was then placed over the coated surface to obtain a laminate consisting of stretched norbornene-based resin film / adhesive composition / stretched norbornene-based resin film. Next, this laminate was subjected to UV irradiation at an integrated light intensity of 400 mJ / cm using a UV irradiation device with a belt conveyor (the lamp was a mercury lamp manufactured by I-Graphics Co., Ltd.). 2 The resin composition was cured by irradiation with ultraviolet light (UV-B). Two stretched norbornene-based resin films were peeled off from the laminate after UV irradiation to obtain resin layers Y-1 to Y-10. The in-plane average refractive index (589 nm) of the obtained resin layers was measured at 25°C using a multi-wavelength Abbe refractometer [DR-M2, manufactured by Atago Co., Ltd.]. The results are shown in Table 2.

[0229] (6) In-plane average refractive index (n1) of resin layer X1 A resin composition (X1) containing acetoacetyl-modified polyvinyl alcohol resin (Gosenor Z200, manufactured by Mitsubishi Chemical Corporation) and water was coated onto one side of a stretched norbornene-based resin film (Zeonor Film, manufactured by Nippon Zeon Co., Ltd.) using an adhesive coating apparatus (manufactured by Daiichi Rika Co., Ltd.) to a dry thickness of 5 μm, and the film was dried at 80°C for 3 minutes to form a resin layer X1. The in-plane average refractive index (589 nm) of the resin layer X1 was measured at 25°C using a multi-wavelength Abbe refractometer (DR-M2, manufactured by Atago Co., Ltd.). The in-plane average refractive index of the resin layer X1 was 1.48. Similarly, the in-plane average refractive index of the resin layer X1' was also 1.48.

[0230] (7) In-plane average refractive index (n1) of resin layer X2 A resin composition (X2) was coated onto one side of a stretched norbornene-based resin film using an adhesive coating device to a thickness of approximately 5 μm after UV irradiation. Another stretched norbornene-based resin film was then placed over the coated surface to obtain a laminate consisting of stretched norbornene-based resin film / adhesive composition / stretched norbornene-based resin film. Next, this laminate was subjected to UV irradiation at an integrated light intensity of 400 mJ / cm using a belt conveyor-equipped UV irradiation device (the lamp was a mercury lamp manufactured by I-Graphics Co., Ltd.). 2 The resin composition was cured by irradiation with ultraviolet light (UV-B). Two stretched norbornene-based resin films were peeled off from the laminate after UV irradiation to obtain resin layer X2. The in-plane average refractive index (589 nm) of the obtained resin layer X2 was measured using a multi-wavelength Abbe refractometer at 25°C. The in-plane average refractive index of resin layer X2 was 1.48.

[0231] (8) In-plane average refractive index (n1) of resin layer X3 A resin composition (X3) containing AP-17 (anionic modified polyvinyl alcohol) and water was coated onto one side of a stretched norbornene-based resin film (Zeonor Film, manufactured by Nippon Zeon Co., Ltd.) using an adhesive coating apparatus [manufactured by Daiichi Rika Co., Ltd.] to a dry thickness of 5 μm. The resin layer X3 was then dried at 80°C for 3 minutes to form the resin layer X3. The in-plane average refractive index (589 nm) of the resin layer X3 was measured at 25°C using a multi-wavelength Abbe refractometer [DR-M2, manufactured by Atago Co., Ltd.]. The in-plane average refractive index of the resin layer X3 was 1.48.

[0232] (9) In-plane average refractive index (n1) of resin layer X4 A resin composition (X4) containing acetoacetyl-modified polyvinyl alcohol resin (Gosenor Film, manufactured by Nippon Zeon Co., Ltd.) and AP-17 in equal parts by mass relative to water was coated onto one side of a stretched norbornene-based resin film (Zeonor Film, manufactured by Nippon Zeon Co., Ltd.) using an adhesive coating apparatus (manufactured by Daiichi Rika Co., Ltd.) to a dry thickness of 5 μm. The resin layer X4 was then dried at 80°C for 3 minutes to form the resin layer X4. The in-plane average refractive index (589 nm) of the resin layer X4 was measured at 25°C using a multi-wavelength Abbe refractometer (DR-M2, manufactured by Atago Co., Ltd.). The in-plane average refractive index of the resin layer X4 was 1.48.

[0233] (10) Refractive index of liquid crystal phase difference film (n3) The in-plane average refractive index of the liquid crystal phase difference film (1) was measured as follows. Using a laminate with the liquid crystal phase difference film (1) (photo-alignment film (2) / liquid crystal phase difference film (1) / acrylic adhesive layer (2) / glass), the in-plane refractive index nx and ny at 589 nm were measured using a KOBRA-WR manufactured by Oji Instruments Co., Ltd. Using nx and ny, the in-plane average refractive index n3 was calculated from the following formula. n3 = (nx + ny) / 2 (In the formula, nx represents the refractive index in the direction of the slow phase axis within the film plane, ny represents the refractive index in the direction of the fast phase axis within the film plane, and n3 represents the in-plane average refractive index.) The in-plane average refractive index of the liquid crystal phase difference film (1) was 1.59.

[0234] (11)|(n1×n3) 1 / 2 -n2|value From the in-plane average refractive index n1 of resin layer X1 or resin layer X2 obtained above, the in-plane average refractive index n3 of the liquid crystal phase difference film (1), and the in-plane average refractive index n2 of each resin layer Y-1 to Y-10, |(n1×n3) 1 / 2 -n2| The value was calculated. The results are shown in Table 2.

[0235] (12) Durability evaluation of optical laminates (moist heat evaluation 1) The laminate (4-1) was cut to a size of 40 mm x 40 mm, the release film on the acrylic adhesive layer (2) side of the laminate (4-1) was peeled off, and the laminate was bonded to a 40 mm x 40 mm alkali-free glass (Corning "EagleXG") to obtain an evaluation sample. A heating experiment was conducted in which the sample was left standing for 168 hours in an environment of 65°C and 90% humidity. The transmittance in the transmission axis direction (Ty1) and the transmittance in the absorption axis direction (Ty2) in the wavelength range of 380 nm to 780 nm before and after the test was measured using the double-beam method with a spectrophotometer (Shimadzu Corporation UV-3150) equipped with a polarizing element holder. The transmittance of the single element was calculated using the following formula. The results are shown in Table 2. Single-unit transmittance (%) = (Ty1 + Ty2) / 2

[0236] Furthermore, luminous efficiency correction was performed according to JIS Z 8701's 2-degree field of view (C light source), and the luminous efficiency correction-only transmittance (Ty3) was calculated. The change in luminous efficiency correction-only transmittance (ΔTy3) was defined as follows. ΔTy3 = |Ty3 (after durability evaluation test) - Ty3 (before durability evaluation test)| Laminate (4-1) was replaced with laminates (4-2) through (4-13) and evaluated similarly. The evaluation criteria were as follows. The results are shown in Table 2. <Evaluation Criteria> A:ΔTy3 ≤ 1.4 B:1.4 <ΔTy3 C: Peeling or lifting occurred during durability testing.

[0237] (13) Evaluation of adhesion Laminate (6-1) was cut to a size of 100 mm x 100 mm, the release film on the acrylic adhesive layer (1) side was peeled off, and it was bonded to a glass plate to obtain an evaluation sample. 100 1 mm x 1 mm grids were formed on the obtained evaluation sample laminate (6-1) using a cutter. Next, cellophane tape (manufactured by Nichiban Co., Ltd.) was applied to the cross-hatch surface, and the cellophane tape was peeled off at a perpendicular angle. The number of grids in the cross-hatch pattern that did not peel or fall out was counted. Laminate (6-1) was replaced with laminates (6-2) to (6-13) and evaluated in the same manner. The evaluation criteria are as follows. The results are shown in Table 2. <Evaluation Criteria> A: The number of squares that have not been peeled off is 90 or more. B: The number of squares that have not been peeled off is 70 or more but less than 90. C: The number of squares that have not been peeled off is less than 70.

[0238] [Table 2]

Claims

1. An optical laminate comprising a polarizing film, a resin layer X, and a resin layer Y adjacent to each other in this order, The polarizing film comprises a cured layer of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound and a dichroic dye. The contact angle of water with respect to the surface of the resin layer X is 90° or less. The resin layer Y is a cured layer of a resin composition (Y) containing a curable compound, wherein the curable composition comprises a polyfunctional (meth)acrylate compound (Y1) having a molecular weight of less than 1000 g / mol, and a (meth)acrylate compound (Y2) having one (meth)acrylic group and one hydroxyl group in its molecule, in an optical laminate.

2. The optical laminate according to claim 1, wherein the resin composition (Y) further comprises a polyfunctional urethane (meth)acrylate compound (Y3) having a weight-average molecular weight of 1000 g / mol or more.

3. The optical laminate according to claim 1, wherein the resin composition (Y) further comprises a (meth)acrylate compound (Y4) having an aromatic ring but no hydroxyl group in its molecule.

4. The optical laminate according to claim 2, wherein the total content of the polyfunctional (meth)acrylate compound (Y1) and the polyfunctional urethane (meth)acrylate compound (Y3) is 10 to 70 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y).

5. The optical laminate according to claim 1, wherein the content of the (meth)acrylate compound (Y2) is 25 to 80 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y).

6. The optical laminate according to claim 3, wherein the content of the (meth)acrylate compound (Y4) is 5 to 25 parts by mass per 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y).

7. The optical laminate according to claim 1, wherein the resin layer X is a cured product layer of a polyvinyl alcohol-based resin composition.

8. The optical laminate according to claim 1, wherein a phase difference film is adjacent to the resin layer Y on the side opposite to the resin layer X, and the phase difference film includes a cured layer of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound.

9. The optical laminate according to claim 8, wherein the phase difference film includes an alignment film, and the alignment film is located on the resin layer Y side.

10. The optical laminate according to claim 1, wherein the resin composition (Y) contains 1 to 10 parts by mass of a polymerization initiator per 100 parts by mass of the total amount of curable compounds contained in the resin composition (Y).

11. The polymerization initiator has a molar extinction coefficient of 10 L·mol at a light source wavelength of 400 nm under acetonitrile solvent. -1 ・cm -1 The optical laminate according to claim 10.

12. When the in-plane average refractive index of the resin layer X is n1, the in-plane average refractive index of the resin layer Y is n2, and the in-plane average refractive index of the phase difference film is n3, then the following equation (1): |(n1×n3) 1/2 --2| ≦ 0.05 (1) The optical laminate according to claim 8, satisfying the requirements.

Citation Information

Patent Citations

  • Bendable optical laminate and method for producing the same

    JP2019203949A

  • Polarizing film, and polarizing plate and display device including the same

    JP2020046622A